Coating film and coating material

A coating film with dispersed nanobubbles addresses the issue of excessive coating weight and cost by reducing the amount of coating material applied, achieving cost-effective protection with minimal weight increase.

JP2024174833APending Publication Date: 2024-12-17HARDOLASS HLDG CO LTD

Patent Information

Application Number
JP2024087589
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-05
Filing Date
2024-05-30
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing coating technologies increase the weight and cost of substrates due to the application of a predetermined thickness of coating films, and there is a need to reduce the amount of coating applied while maintaining protective properties.

Method used

The introduction of a coating film with dispersed nanobubbles, where the nanobubbles are ultrafine spherical spaces within the coating, reducing the volume and weight of the coating applied by dispersing them at a concentration of 10 to 95 vol.%, with an average particle size of less than 1 μm, thereby minimizing the amount of coating material needed.

Benefits of technology

The coating film effectively reduces the amount of coating material applied per unit area, lowering costs and minimizing the increase in substrate weight while maintaining protective properties against damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174833000001_ABST
    Figure 2024174833000001_ABST
Patent Text Reader

Abstract

To provide a coating film capable of reducing a coating amount to a surface of a substrate being a coating object, the coating film capable of coating the surface of the substrate inexpensively.SOLUTION: A coating film 13 (a fluororesin coating film 13, a silicon resin coating film 13, an acrylic resin coating film 13, a urethane resin coating film 13) is configured to coat a surface 12 of a substrate 11 being a coating object in a cured state. Inside the coating film 13, nanobubbles with an average particle diameter D90 of less than 1 μm, preferably, an average particle diameter D50 within a range of 1 nm to less than 500 nm, are dispersed and mixed (dispersed and dissolved) in a prescribed density. The nanobubbles are made of a gas mixture of one or two or more kinds from among air, ozone, helium, oxygen, nitrogen, carbon dioxide and argon. In the inorganic coating film 13, a content rate of the nanobubbles 14 is within a range of 10 to 95 vol.%. A total number of nanobubbles per 1 mm2 of the coating film 13 is within a range of 107 to 1012 bubbles / 1 mm2.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating film that is applied to the surface of a substrate to be coated, and a paint that forms the coating film. [Background technology]

[0002] A fluorine-containing polymer and a polymer having a first crosslinkable group and a kinetic viscosity of 30 to 150 mm 2 A coating material containing polydimethyl silicone of 1 / s, an acrylic silicone having a second crosslinkable group, and a curing agent having a reactive group capable of reacting with the first crosslinkable group and the second crosslinkable group has been disclosed (see Patent Document 1). By using this coating material, it is possible to create an antifouling coating film with excellent warm water resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-52716 A Summary of the Invention [Problem to be solved by the invention]

[0004] It is preferable that the coating material can be applied inexpensively by reducing the amount of coating material applied to the surface of the substrate to be coated. However, since the coating film can protect the surface of the substrate by applying a predetermined thickness to the surface of the substrate to be coated, it is necessary to ensure a predetermined thickness of the coating film after the applied coating material has hardened, and the amount of coating material cannot be reduced unconditionally. Furthermore, when the specific surface area of ​​the substrate to which the coating material is applied is large and the coating material is applied to the entire substrate, the weight of the substrate including the coating film of the hardened coating material increases.

[0005] An object of the present invention is to provide a coating film that can be applied inexpensively to the surface of a substrate to be coated, by reducing the amount of coating applied to the surface of the substrate. Another object of the present invention is to provide a coating film that can minimize the increase in weight of the substrate including the coating film when applied to the surface of the substrate to be coated. Another object of the present invention is to provide a coating material that can be applied inexpensively, by reducing the amount of coating applied to the surface of a substrate to be coated. Another object of the present invention is to provide a coating material that can form a coating film that can minimize the increase in weight of the substrate. [Means for solving the problem]

[0006] The first premise of the present invention for solving the above problems is a coating film that is applied in a cured state to the surface of a substrate to be coated.

[0007] As a first feature of the present invention in the first premise, a large number of minute, independent spherical spaces are dispersed and mixed inside the coating film.

[0008] As an example of the present invention having the first characteristic, the spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed (dispersed and dissolved) inside the coating at a specified concentration.

[0009] As another example of the present invention having the first characteristic, the average particle diameter D of nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The nanobubbles are dispersed and mixed at a specified concentration inside the coating film.

[0010] In another example of the present invention having the first characteristic, the content of nanobubbles in the coating film is in the range of 10 to 95 vol. %.

[0011] As another example of the present invention having the first characteristic, the coating film is any one of a fluororesin coating film made from a fluororesin paint, a silicone resin coating film made from a silicone resin paint, an acrylic resin coating film made from an acrylic resin paint, and a urethane resin coating film made from a urethane resin paint.

[0012] In another example of the present invention having the first characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these.

[0013] The second premise of the present invention for solving the above problem is a coating material that is applied to the surface of a substrate to be coated and forms a coating film on the surface of the substrate.

[0014] As a second feature of the present invention in the second premise, a large number of minute, independent spherical spaces are dispersed and mixed inside the paint.

[0015] As an example of the present invention having the second characteristic, the spherical space is formed by nanobubbles, and the average particle diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed (dispersed and dissolved) in the paint at a specified concentration.

[0016] As another example of the present invention having the second characteristic, the nanobubbles are dispersed and mixed into the paint in a negatively charged state, and the average particle diameter of the nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 Nanobubbles are dispersed and mixed in the paint at a specified concentration.

[0017] In another example of the present invention having the second characteristic, the content of nanobubbles in the coating material is in the range of 10 to 95 vol. %.

[0018] As another example of the present invention having the second characteristic, the paint is any one of a fluororesin paint, a silicon resin paint, an acrylic resin paint, and a urethane resin paint, and the kinetic viscosity of the paint is 50 to 200 mm 2 / s, and the rising speed of nanobubbles inside the paint at 20°C is in the range of 0·000015 to 0.00005 mm / min.

[0019] In another example of the present invention having the second characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these. Effect of the Invention

[0020] According to the coating film of the present invention, a large number of independent fine spherical spaces are dispersed (dispersed and dissolved) inside the coating film, so the proportion of the coating film itself per unit area of ​​the coating film can be reduced by the large number of fine spherical spaces, and the amount of coating film itself applied when the surface of the substrate to be coated is reduced, so the amount of coating film applied to the substrate can be reduced, and the coating amount can be reduced compared to when the coating film does not have spherical spaces dispersed therein, so that the surface of the substrate can be coated inexpensively with the coating film. Compared to when the coating film does not have spherical spaces dispersed therein, the mass per unit area of ​​the coating film is reduced, so that when the coating film is applied to the surface of the substrate to be coated, the increase in the weight of the substrate including the coating film can be minimized. Even if the substrate to which the coating film is applied is damaged in various ways, the coating film can protect the substrate from various damages and prevent the substrate from deteriorating due to such damages.

[0021] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90is less than 1 μm, and its average particle size D 90 A coating film in which nanobubbles of the above are dispersed (dispersed and dissolved) at a specified concentration inside the coating film has nanobubbles of average diameter D 90 By dispersing nanobubbles with sizes of less than 1 μm at a specified concentration, the proportion of the coating itself per unit area of ​​the coating can be reduced by the ultrafine bubbles, and the amount of coating itself applied when the surface of the substrate to be coated is reduced, making it possible to reduce the amount of coating applied to the substrate, and the reduced amount of coating applied reduces the unit price of the coating per unit area of ​​the substrate surface compared to when nanobubbles are not dispersed in the coating, making it possible to coat the surface of an article inexpensively with a coating. Since the mass per unit area of ​​the coating is reduced compared to when nanobubbles are not dispersed (dissolved) in it, the coating has a smaller mass per unit area, and when the coating is applied to the surface of the substrate to be coated, the increase in the weight of the substrate including the coating can be minimized.

[0022] Average diameter of nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 A coating film in which nanobubbles of the above are dispersed (dissolved) at a specified concentration inside the coating film has an average particle size of D 50 Since nanobubbles having sizes in the range of 1 nm or more and less than 500 nm are dispersed and mixed in a large amount at a predetermined concentration inside the coating film, the proportion of the coating film itself per unit area in the coating film can be reduced by the ultrafine bubbles of nanobubbles, and the amount of the coating film itself applied when coating the surface of the substrate to be coated with a coating film can be reliably reduced. Furthermore, the reduced amount applied reduces the unit price of the coating film per unit area of ​​the substrate surface, making it possible to coat the surface of the substrate with a coating film at low cost.

[0023] A coating film having a nanobubble content in the range of 10 to 95 vol. % has a nanobubble content in the coating film in which nanobubbles are dispersed and mixed within the above range, so that ultrafine nanobubbles are dispersed and mixed in large quantities at a predetermined concentration inside the coating film, and the proportion of the coating film itself per unit area in the coating film can be reduced by the ultrafine nanobubbles, and the amount of the coating film itself applied when the surface of the substrate to be coated is applied with the coating film can be reliably reduced. Furthermore, the reduced amount applied reduces the unit price of the coating film per unit area of ​​the substrate surface, making it possible to coat the substrate surface with a coating film at low cost.

[0024] The coating film is any one of a fluororesin coating film made from a fluororesin paint, a silicone resin coating film made from a silicone resin paint, an acrylic resin coating film made from an acrylic resin paint, and a urethane resin coating film made from a urethane resin paint. A large number of nanobubbles (spherical spaces) of ultrafine air bubbles are dispersed and mixed (dispersed and dissolved) inside the fluororesin coating film, silicone resin coating film, acrylic resin coating film, or urethane resin coating film. The proportion of the fluororesin coating film, silicone resin coating film, acrylic resin coating film, or urethane resin coating film per unit area can be reduced by the ultrafine air bubbles, i.e., the amount of the coating film itself applied when the surface of a substrate to be coated with the coating film is reduced, and the amount of the coating film applied to the substrate can be reduced. At the same time, the reduced amount of coating reduces the unit price of the coating film per unit area of ​​the substrate surface, and the surface of an article can be coated with the coating film at low cost. Even if a substrate coated with a fluororesin coating film, a silicone resin coating film, an acrylic resin coating film, or a urethane resin coating film is damaged in various ways, the coating film can protect the substrate from various types of damage and prevent deterioration of the substrate due to such damage.

[0025] In a coating film in which the gas forming the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these, a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the exemplified gases or mixed gases of these gases are dispersed and mixed (dispersed and dissolved) inside the coating film, and the proportion of the coating film itself per unit area of ​​the coating film can be reduced by the ultrafine bubbles (spherical spaces). This reduces the amount of coating film itself applied when the surface of the substrate to be coated with the coating film is applied, and the amount of coating film applied to the substrate can be reduced. At the same time, the reduced amount of coating reduces the unit price of the coating film per unit area of ​​the substrate surface, and the substrate surface can be coated with the coating film at low cost.

[0026] According to the paint of the present invention, a large number of independent fine spherical spaces are dispersed (dispersed and dissolved) inside the paint, so that the ratio of the paint itself per unit volume of the paint can be reduced by the spherical spaces, and the amount of paint applied when the paint is applied to the surface of the substrate to be applied is reduced, and the amount of paint applied to the substrate can be reduced. In addition, the reduced amount of paint applied reduces the unit price of the paint per unit area of ​​the substrate surface compared to when the spherical spaces are not dispersed and mixed therein, and the paint can be applied inexpensively. Since the mass per unit volume of the paint is reduced compared to when the spherical spaces are not dispersed (dispersed and dissolved) therein, when the paint is applied to the surface of the substrate to be applied, the increase in the weight of the substrate including the coating film formed from the paint can be minimized. Even if the substrate to which the coating film formed from the paint is applied is damaged in various ways, the coating film can protect the substrate from various damages, and the deterioration of the substrate due to such damage can be prevented.

[0027] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D90 A paint in which nanobubbles of the given concentration are dispersed (dispersed and dissolved) has an average particle size of D 90 By dispersing and mixing nanobubbles with sizes less than 1 μm at a specified concentration, the proportion of the paint itself per unit volume of the paint can be reduced by the nanobubbles, and the amount of paint applied when applied to the surface of the substrate to be coated is reduced, making it possible to reduce the amount of paint applied to the substrate, and the reduced amount applied reduces the unit price of paint per unit area of ​​the substrate surface compared to when nanobubbles are not dispersed in the paint, making it possible to apply the paint that forms the coating film at low cost. Compared to when nanobubbles are not dispersed and mixed in the paint, the mass per unit volume of the paint is reduced, and when it is applied to the surface of the substrate to be coated, the increase in the weight of the substrate including the coating film formed from the paint can be minimized.

[0028] The negatively charged nanobubbles are dispersed and mixed into the paint, and the average diameter of the nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 In paints in which nanobubbles are dispersed (dispersed and dissolved) at a specified concentration within the paint, the nanobubbles are negatively charged, so the nanobubbles dispersed within the paint repel each other and do not bond (coalesce), preventing the nanobubbles from bonding together and forming giant bubbles, and maintaining the dispersed state of the ultrafine nanobubbles in the paint that makes up the coating. Since the ultrafine nanobubbles are dispersed (dispersed and dissolved) within the paint without bonding together, the nanobubbles are less likely to volatilize from the paint, and the nanobubbles can remain in the paint for a long period of time. The paint has an average particle size of D 50 Since a large amount of nanobubbles with sizes in the range of 1 nm or more and less than 500 nm are dispersed and mixed into the paint at a specified concentration, the proportion of paint itself per unit volume in the paint can be reduced by the use of ultra-fine nanobubbles, and the amount of paint itself to be applied when the paint is applied to the surface of a substrate to be coated can be reliably reduced.

[0029] A paint having a nanobubble content in the range of 10 to 95 vol. % has a nanobubble content in the paint in which nanobubbles are dispersed and mixed (dispersed and dissolved) within the above range, and a large amount of ultrafine nanobubbles are dispersed and mixed into the paint at a specified concentration. The proportion of the paint itself per unit volume in the paint can be reduced by the ultrafine nanobubbles, and the amount of paint itself to be applied when the paint is applied to the surface of the substrate to be coated can be reliably reduced. Furthermore, the reduced amount applied reduces the unit price of the paint per unit area of ​​the substrate surface, making it possible to apply the paint that forms the coating film inexpensively.

[0030] The paint is either a fluororesin paint, a silicon resin paint, an acrylic resin paint, or a urethane resin paint, and the kinetic viscosity of the paint is 50 to 200 mm 2 In a paint in which the kinetic viscosity of the paint in which the nanobubbles are dispersed (dissolved) is in the above range and the rate of rise of the nanobubbles in the paint at 20°C is in the above range, the nanobubbles are unlikely to volatilize from the paint, the nanobubbles can be allowed to remain in the paint for a long period of time, and the amount of paint applied when the paint is applied to a substrate to be coated can be reliably reduced. Since the paint is any of fluororesin paint, silicone resin paint, acrylic resin paint, and urethane resin paint, even if a substrate coated with a fluororesin coating film made from a fluororesin paint, a silicone resin coating film made from a silicone resin paint, an acrylic resin coating film made from an acrylic resin paint, or a urethane resin coating film made from a urethane resin paint is damaged in various ways, the coating film made from the paint can protect the substrate from various damages, and deterioration of the substrate due to the damage can be prevented.

[0031] In paints in which the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these, a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the example gases or mixed gases of these gases are dispersed and mixed (dispersed and dissolved) inside the paint, and the proportion of the paint itself per unit volume of the paint can be reduced by the ultrafine nanobubbles (spherical spaces). This reduces the amount of paint applied when the paint is applied to the surface of a substrate to be coated, and the amount of paint applied to the substrate can be reduced. At the same time, the reduced amount of paint applied reduces the unit price of the paint per unit area of ​​the substrate surface, and the paint that forms the coating can be applied inexpensively. [Brief description of the drawings]

[0032] [Figure 1] FIG. 1 is a configuration diagram showing an example of a nanobubble generating device that mixes nanobubbles into paint. [Diagram 2] FIG. 2 is an image diagram showing an example of the structure of a fluororesin coating film. [Diagram 3] FIG. 2 is an image diagram showing an example of the structure of a silicone resin coating film. [Figure 4] A diagram showing an image of nanobubbles dispersed and mixed (dispersed and dissolved) inside a coating film. [Diagram 5] A diagram explaining the drying process of emulsion-based paint. [Figure 6] A diagram explaining the drying process of solvent-based paint. [Figure 7] FIG. 2 is a graph showing the porosity, total number of nanobubbles, and nanobubble diameter of the coating films of Samples (A) to (H). [Figure 8] FIG. 2 is a graph showing the porosity, total number of nanobubbles, and particle size of the coating films of samples (I) to (P). [Figure 9] FIG. 1 shows the evaluation of adhesion, scratch hardness, abrasion resistance, and mass increase of the coating film of samples (A) to (H). [Figure 10] FIG. 1 shows the evaluation of adhesion, scratch hardness, abrasion resistance, and mass increase of the coating film of samples (I) to (P). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The paint and coating film according to the present invention will be described in detail below with reference to the accompanying drawings. FIG. 1 is a block diagram showing an example of a nanobubble generator 15 for mixing nanobubbles 14 into a paint 10, and FIG. 2 is an image showing an example of the structure of a fluororesin coating film 13. FIG. 3 is an image showing an example of the structure of a silicon resin coating film 13, and FIG. 4 is an image showing nanobubbles 14 dispersed and mixed (dispersed and dissolved) inside the coating film 13. FIG. 5 is a diagram explaining the drying process of an emulsion-based paint 10, and FIG. 6 is a diagram explaining the drying process of a solvent-based paint 10. In FIG. 4, the nanobubbles 14 are illustrated as an image that can be seen with the naked eye, but in reality, the nanobubbles 14 cannot be seen with the naked eye.

[0034] (Paint 10 and Coating 13) The paint 10 is applied to a surface 12 (external surface, internal surface) of a substrate 11 (various articles) to be coated. The hardened paint 10 forms a coating film 13 that is applied to the surface 12 of the substrate 11. As the paint 10, any of fluororesin paint, silicon resin paint (silicone resin), acrylic resin paint, and urethane resin paint is used. The interior (within the paint 10) of the paint 10 (fluororesin paint, silicon resin paint, acrylic resin paint, urethane resin paint) contains particles of average particle size D 90 is less than 1 μm, preferably the average particle size D 50 Nanobubbles 14 (ultrafine bubbles) (numerous independent tiny spherical spaces) in the range of 1 nm or more and less than 300 nm are dispersed and mixed (dispersed and dissolved) at a specified concentration.

[0035] The fluororesin paint is applied to the surface 12 of the substrate 11 and then hardens to form a fluororesin coating film having a predetermined thickness. The silicone resin paint is applied to the surface 12 of the substrate 11 and then hardens to form a silicone resin coating film having a predetermined thickness. The acrylic resin paint is applied to the surface 12 of the substrate 11 and then hardens to form an acrylic resin coating film having a predetermined thickness. The urethane resin paint is applied to the surface 12 of the substrate 11 and then hardens to form a urethane resin coating film having a predetermined thickness.

[0036] Fluorine resin paint is a paint whose main component is fluororesin. The fluororesin that is the main component of fluororesin paint is one of PTFT (polytetrafluoroethylene), PFA (perfluoroalkoxyalkane polymer), FEP (perfluoroethylenepropene copolymer), and ETFE (ethylene-tetrafluoroethylene copolymer), or a solution of a blend of two or more of these resins. In addition, as the fluororesin, a high-temperature modified type that increases the adhesion to the surface 12 of the substrate 11 without decreasing its heat resistance and improves abrasion resistance can be used, and a low-temperature modified type that can be processed at low temperatures while taking advantage of the low friction and non-stickiness of the fluororesin can also be used.

[0037] The molecular structure of PTFT (polytetrafluoroethylene) is represented by the following general formula (Chemical Formula 1).

[0038] [ka] PTFT has a molecular structure in which carbon atoms (C) and fluorine atoms (F) are linked in a linear chain, and the bonds between the carbon atoms are covered with fluorine atoms without any gaps, so that they are protected by the fluorine atoms. The arrangement of atoms in the PTFT molecule is tight and symmetrical, and the polarization of the electric charge is very small. Furthermore, it is a polymer made of a very long molecular chain with a molecular weight of one million to tens of millions. PTFT, which is stable due to such a characteristic molecular structure, forms a coating film 13 that has excellent non-adhesiveness, water and oil repellency, low friction, heat resistance, chemical resistance, electrical properties, flame retardancy, and weather resistance. PTFT has a density of 2.13 to 2.20 g / cm 3 Its room temperature hardness is F~2H, and its water repellency angle (°) water / oil (nHD) is 110-115 / 45-50.

[0039] The molecular structure of PFA (perfluoroalkoxyalkane polymer) is represented by the following general formula (Chemical Formula 2).

[0040] [ka] PFA is a copolymer of tetrafluoroethylene (TFE) and perfluoroalkyl vinyl ether (PFVE), and its main features are its low viscosity when melted and its properties comparable to those of PTFTE. Like PTFT, it has excellent heat resistance with a continuous use temperature of 260°C, and is not affected by most chemicals such as strong acids, strong alkalis, and organic solvents. PFA forms a coating film 13 that has excellent non-adhesiveness, heat resistance, cold resistance, water repellency, chemical resistance, electrical properties, flame retardancy, and weather resistance. PFA has a room temperature hardness of F to H, and its water repellency angle (°) water / oil (nHD) is 110-115 / 45-50.

[0041] The molecular structure of FEP (perfluoroethylene propene copolymer) is represented by the following general formula (Chemical Formula 3).

[0042] [ka] FEP is a copolymer of tetrafluoroethylene (TFE) and hexafluoropropylene (HFP), and has the trifluoromethyl group CF3 in its molecular chain, giving it the same non-stickiness and chemical resistance as PTFE, while also having a low melting point. Since FEP has a low melt viscosity, when used for coating, it can produce a continuous film without pinholes. FEP has a density of 2.15 to 2.17 g / cm 3 Its room temperature hardness is in the range of F to H, and its water repellency angle (°) water / oil (nHD) is 110-115 / 45-50.

[0043] The molecular structure of ETFE (ethylene-tetrafluoroethylene copolymer) is represented by the following general formula (Chemical Formula 4).

[0044] [ka] ETFE is a copolymer of tetrafluoroethylene and ethylene, and contains hydrogen atoms (H) in its molecular structure. Therefore, compared with PTFE and FEP, it has low chemical resistance and heat resistance, and its continuous use temperature is 150°C. On the other hand, its mechanical strength is high, and it can be processed at a low melting point. It has a density of 1.73 to 1.75 g / cm 3 is in the range.

[0045] Silicone resin paint is a paint whose main component is silicone resin. The molecular structure of silicone resin, the main component of silicone resin paint, is expressed by the following general formula (Chemical Formula 5).

[0046] [ka] Silicone resin paint has excellent durability, water resistance, chemical resistance, and flexibility, and forms a coating film (three-dimensional glass skeleton coating) with high adhesion to the surface 12 of the substrate 11. Silicone resin coatings made from silicone resin paints are composed of siloxane bonds (Si-O, silicon-oxygen) and contain several silicates (SiO4 / 2) or silsesquioxanes (R-SiO3 / 2). R is various alkyl groups or allyl groups, and typical functional groups are methyl or phenyl groups. Compared to organic resins composed of carbon bonds (CC), they are more resistant to decomposition by heat or radiation. The resistance of silicone resin coatings is due to the strength of the oxygen-hydrogen bonds (carbon-carbon bonds are 82.6 Kcal / mole, while silicon-oxygen bonds are 108 Kcal / mole), their property of transmitting visible light and ultraviolet light, and their inherently partially oxidized structure.

[0047] By adding organic functional groups, the siloxane polymer has a more linear structure, and the physical properties (e.g., flexibility) and performance derived from the organic functional groups are imparted. The introduction of phenyl groups into the siloxane skeleton increases compatibility with organic resins, increases toughness, and maintains thermal stability at medium temperatures (250°C). On the other hand, the methyl groups provide improved curing properties, resistance to thermal shock, and reduced weight loss at humidity limits. Silicone polymer coating solutions (silicone resins) are produced by hydrolysis of chlorosilanes or alkoxysilanes, forming highly reactive silanol groups (Si-OH) in the process. RSiC13+3H2ORSi(OH)3+3HCl, RSi(OR')3+3H2ORSi(OH)3+3R'OH In the initial condensation reaction, a siloxane oligomer structure is formed. 2 RSi(OH)3RSi(OH)2-O-SiR(OH)2+H2O, and as the condensation reaction progresses, a three-dimensional crosslinked siloxane structure is formed. By introducing heat and a catalyst into the condensation reaction, the molecular weight increases and the physical properties are improved. On the other hand, the viscosity of the polymer increases, making it necessary to dilute and dissolve it in a solvent. Similarly, in cases where application characteristics are required, the hydroxyl groups of the organic resin (e.g., polyester) can be reacted with silanol groups and alkoxy groups to form a silicone-organic resin composite resin, and the performance can be improved depending on the degree of siloxane modification. Cold blending of the resin intermediate and the organic resin can be carried out with a small amount of solvent. However, a higher and longer heat curing process is required to advance the reaction and ensure curing. In addition to the selection of the optimal silicone resin, other ingredients in the formulation play an important role in the performance of the coating.

[0048] When making a prototype silicone resin paint, the first step is to clarify the required characteristics for the intended application and determine which resin binder can be used. The heat, chemicals, and ultraviolet rays to which the silicone resin paint will be exposed during curing, as well as the required physical properties, also affect the selection of the resin binder. Silicone resin paint (silicone resin) contributes to improving the heat resistance, chemical resistance, and durability against ultraviolet rays of the silicone resin coating, but other performance and physical properties can also be imparted by combining silicone with a specific organic binder (coating hardness: phenols and melamine resins, room temperature drying: acrylic resins, corrosion resistance: epoxy resins, toughness: alkyd resins). The amount of silicone in the coating formulation is determined according to the performance requirements for the application.

[0049] Silicone resin paints include the formulation components of catalyst, curing conditions, solvent and thinner. Silanol-functional resins are heat cured without the addition of catalyst. However, the addition of metal driers (e.g. zinc, iron, cobalt octoate) accelerates the curing rate. The usual catalyst addition amount is 0.1-0.2% of the metal based on the resin solids. Silicone resin paints formulated with silanol-functional silicone resins require heat curing to achieve optimal coating performance, but the curing rate varies depending on the silicone content and the curing conditions of other major ingredients. The curing method for 100% silicone resin systems is 232°C (450°F) for 30 minutes or 204° (400°F) for 60 minutes. Silicone resin paints (silicone resins) can use aromatic hydrocarbons (e.g. toluene, xylene), ketones, esters, acetates, and chlorine-based solvents as solvents. Small additions (<5%) of glycol ethers and alcohols (eg butanol) improve the stability of silicone resins.

[0050] Acrylic resin paint is a paint whose main component is acrylic resin. Acrylic resin paint forms an acrylic resin coating film with excellent weather resistance, gloss, transparency, water resistance, adhesion, and corrosion resistance. Water-based acrylic resin and solvent-based acrylic resin can be used for the acrylic resin. For water-based acrylic resin, acrylic emulsion, acrylic-styrene emulsion, hydroxyl group-containing acrylic emulsion, room temperature drying water-soluble acrylic resin, baking type acrylic dispersion, hydroxyl group-containing acrylic dispersion, etc. can be used. For solvent-based acrylic resin, isocyanate-curing acrylic resin, room temperature / forced drying acrylic resin, melamine baking acrylic resin, moisture-curing silicon acrylic resin, etc. can be used. For organic solvent, dibutyl ether, turpentine oil, benzene, toluene, etc. can be used.

[0051] The urethane resin paint is composed of a polyol having multiple hydroxyl groups as a main component and a polyisocyanate. The urethane resin paint may be an acrylic urethane paint having an acrylic polyol as a main component. The urethane resin paint may also contain an acrylic polyol and cellulose acetate butyrate. The urethane resin paint forms a urethane resin coating film having excellent coating performance, finish, weather resistance, adhesion, flexibility, and chemical resistance. The urethane resin paint can be diluted with an organic solvent. As the organic solvent, an alcohol-based, carboxylic acid ester-based, ketone-based, amide-based, aliphatic, and aromatic hydrocarbon-based solvents, etc., are used.

[0052] The polyols used include 1,6-hexanediol, cyclohexyldimethanol, neopentyl glycol, butylethylpropanediol, trimethylolethane, trimethylolpropane, polycaprolactone triol, ditrimethylolpropane, pentaerythritol, polycaprolactone tetraol, dipentaerythritol, sorbitol, mannitol, etc. Also, a mixture of at least two of these may be used.

[0053] For the polyisocyanate, a bifunctional or higher isocyanate compound is used. As the bifunctional isocyanate compound, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4-dicyclohexyl diisocyanate, etc. are used. As the trifunctional or higher isocyanate compound, a biuret, trimethylolpropane adduct, isocyanurate, allophanate, etc. are used, which are synthesized using a diisocyanate compound as a starting material. In order to increase the crosslink density of the urethane resin coating film made from the urethane resin paint and improve the weather resistance and contamination resistance of the coating film, it is preferable that the polyisocyanate is a trifunctional or higher isocyanate compound.

[0054] Examples of trifunctional or higher isocyanate compounds include hexamethylene diisocyanate biuret, hexamethylene diisocyanate adduct, hexamethylene diisocyanate isocyanurate, blocked isocyanate, 1,3-bis(isocyanatomethyl)cyclohexane trimethylolpropane adduct, 1,3-bis(isocyanatomethyl)cyclohexane isocyanurate, isophorone diisocyanate trimethylolpropane adduct, hexamethylene diisocyanate allophanate, etc. Also, a mixture of at least two of these isocyanate compounds is used.

[0055] Fluorine resin paints, silicone resin paints, acrylic resin paints, and urethane resin paints contain various additives and pigments as necessary. Additives include matting agents that reduce the gloss of the coating film, surfactants that prevent the decrease in surface tension, drip prevention agents that prevent the coating from running off, color separation prevention agents that prevent color unevenness caused by mixing pigments, preservatives and antifungal agents that prevent corrosion of the coating film, plasticizers that improve the flexibility and adhesion of the coating, anti-skinning agents that prevent the skin that occurs on the surface during storage of the coating, and leveling agents that ensure the fluidity of the coating film. Additives include hardeners that harden the coating film and improve weather resistance, water resistance, chemical resistance, heat resistance, etc. Hardeners include blocked isocyanates such as hexamethylene isocyanate trimer or their emulsified dispersions, melamine resins such as methylated melamine, methylolated melamine, and butyrolated melamine, and urea resins such as methylated urea and butylated urea. Pigments include inorganic color pigments, organic color pigments, and extender pigments. Fluorine resin paints, silicon resin paints, acrylic resin paints, and urethane resin paints include either water-based or oil-based paints, and also include either one-component or two-component paints. Other additives may include film-forming aids, thickeners, light stabilizers, design agents, surface conditioners, and aqueous media. The aqueous media are used to dilute the aqueous dispersion. As thickeners, urethane-based thickeners, polyacrylic-based thickeners, polyamide-based thickeners, cellulose-based thickeners, and thickeners of clay minerals such as bentonite are used. The water contact angle of a fluororesin coating film made from a fluororesin paint, a silicone resin coating film made from a silicone resin paint, an acrylic resin coating film made from an acrylic resin paint, and a urethane resin coating film made from a urethane resin paint is 60° or less. The water contact angle is measured by dropping a water drop with a diameter of 1 to 2 mm on the coating film, and the water drop is photographed after 30 seconds with a video camera and image analysis is performed. The water contact angle is twice the angle between the line connecting the apex and end point of the water drop and the coating film.

[0056] (Nanobubble mixing device 15) As shown in Fig. 1, an example of the nanobubble mixing device 15 is composed of a paint storage tank 16 having a predetermined volume, a gas supply tank 17, a water supply pump 18, an air supply pump 19, a static fluid mixer 20 (nanobubble generator), a coating liquid storage tank 21 having a predetermined volume and storing the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed, a cooling device (not shown), and a controller (not shown). The nanobubble mixing device 15 is supplied with power from a power source (not shown). The coating liquid storage tank 16 stores any one of the above-mentioned fluororesin paint, silicon resin paint, acrylic resin paint, and urethane resin paint (paint before the nanobubbles 14 are dispersed and mixed (dispersed and dissolved)).

[0057] A level gauge (not shown) is installed in the paint storage tank 16. The level gauge is connected to the controller via a signal line, measures the level (storage volume) of the paint 10 (fluororesin paint, silicon resin paint, acrylic resin paint, urethane resin paint) stored in the paint storage tank 16, and transmits the measured level to the controller. The paint storage tank 16 is connected to the water supply pump 18 via a water supply pipe 22 (water supply pipe). Although not shown, a flow meter, a check valve, and a water supply solenoid valve are installed in the water supply pipe 22. The flow meter is connected to the controller via a signal line, measures the flow rate of the coating liquid 10 flowing through the water supply pipe 22, and transmits the measured flow rate to the controller. The control unit of the water supply solenoid valve is connected to the controller via a signal line, and its start / stop (open / close) is controlled by the controller.

[0058] The gas supply tank 17 contains a gas to be dispersed and mixed into the coating liquid 10 at a predetermined pressure. The gas to be dispersed and mixed into the coating liquid 10 may be any one of air, ozone, helium, oxygen, nitrogen, carbon dioxide, and argon, or a mixed gas of two or more of them. The gas supply tank 17 is connected to a mixing line 24 (mixing pipe) via an air supply line 23 (air supply pipe). Although not shown, a barometer, a check valve, and an air supply solenoid valve are installed in the air supply line 23. The barometer is connected to a controller via a signal line, measures the air pressure of the gas contained in the gas supply tank 17, and transmits the measured air pressure to the controller. The control unit of the air supply solenoid valve is connected to the controller via a signal line, and its start / stop (open / close) is controlled by the controller. The air supply line 23 contains an air supply pump 19. The control unit of the air supply pump 19 is connected to the controller via a signal line. The start / stop and output of the air supply pump 19 are controlled by a controller.

[0059] The water supply pump 18 is installed in a water supply pipe 22, and its control unit is connected to the controller via a signal line. The start / stop and output of the water supply pump 18 are controlled by the controller. The water supply pump 18 is connected to a static fluid mixer 20 via a mixing pipe 24. The static fluid mixer 20 is connected to a coating liquid storage tank 21 of a predetermined volume via a supply pipe 25. A level meter (not shown) is installed in the coating liquid storage tank 21. The level meter is connected to the controller via a signal line, measures the level (storage volume) of the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed and stored in the coating liquid storage tank 21, and transmits the measured level to the controller.

[0060] The static fluid mixer 20 (nanobubble generator) is formed of a cylindrical unit 26 having an inlet and an outlet, and a plurality of honeycomb structure elements (agitation blades) (not shown) arranged inside the cylindrical unit 26. These honeycomb structure elements are arranged in a state of being connected in series inside the cylindrical unit 26. The static fluid mixer 20 (nanobubble generator) passes the paint 10 and gas through the inside of the honeycomb structure element by centrifugal force generated by high-speed rotation, thereby ultra-finely reducing the gas to the nano level to generate nanobubbles 14, and simultaneously mixes (dissolves) the generated nanobubbles 14 evenly and uniformly into the paint 10, producing paint 10 in which the nanobubbles 14 are evenly and uniformly dispersed and mixed (dispersed and dissolved) throughout. In the static fluid mixer 20, the paint 10 and gas pass through the inside of the honeycomb structure element many times, which causes the gas to be ultrafine (to nano level) and the ultrafine gas to be mixed (dissolved) into the paint 10. The cooling device cools the cylindrical unit 26 of the static fluid mixer 20 to a set temperature by circulating a refrigerant (e.g., hydrofluorocarbon). The control unit of the cooling device is connected to the controller via a signal line. The start / stop and output of the cooling device are controlled by the controller.

[0061] The controller is a physical computer that has a central processing unit (CPU or MPU) and memory (main memory and cache memory), runs on an independent operating system (OS), and is equipped with a large-capacity storage area. Input devices such as a keyboard and mouse, and output devices such as a display and printer are connected to the controller via an interface. The central processing unit of the controller starts a nanobubble mixing application stored in the memory based on the control of the operating system (OS), and performs the mixing operation of dispersing and mixing (dispersing and dissolving) nanobubbles 14 into the paint 10 according to the application.

[0062] When the switch of the nanobubble mixing device 15 is turned on, a mixing operation is started to mix nanobubbles 14 into the paint 10 (fluororesin paint, silicon resin paint, acrylic resin paint, urethane resin paint) stored in the paint storage tank 16. A predetermined amount of paint 10 is poured into the paint storage tank 16, and gas (one of air, ozone, helium, oxygen, nitrogen, carbon dioxide, and argon, or a mixed gas of two or more of them) is stored at a predetermined pressure in the gas supply tank 17. When the switch of the nanobubble mixing device 15 is turned on, the controller sends a water supply signal to the control unit of the water supply pump 18, sends an air supply signal to the control unit of the air supply pump 19, and sends a cooling signal to the control unit of the cooling device. Furthermore, the controller sends an open signal to the control unit of the water supply solenoid valve, sends an open signal to the control unit of the air supply solenoid valve, and sends measurement signals to the level meter, flow meter, and barometer.

[0063] The control unit of the water supply pump 18 that has received the water supply signal starts the water supply pump 18 at a predetermined output (set output), and the control unit of the air supply pump 19 that has received the air supply signal starts the air supply pump 19 at a predetermined output (set output). The control unit of the cooling device that has received the cooling signal starts the cooling device at a predetermined output (set output). The control unit of the water supply solenoid valve that has received the open signal opens the water supply solenoid valve, and the control unit of the air supply solenoid valve that has received the open signal opens the air supply solenoid valve. The level meter that has received the measurement signal starts measuring the level of the paint 10 stored in the paint storage tank 16, and the flow meter that has received the measurement signal starts measuring the flow rate of the paint 10 flowing through the water supply pipe 22. The barometer that has received the measurement signal starts measuring the air pressure of the gas flowing through the air supply pipe 23.

[0064] The paint 10 stored in the paint storage tank 16 is forcibly supplied from the paint storage tank 16 to the static fluid mixer 20 by starting the water supply pump 18 (paint water supply process). The paint 10 flows from the water supply pipe 22 through the water supply pump 18 into the mixing pipe 24, and flows through the mixing pipe 24 into the static fluid mixer 20. The gas stored in the gas supply tank 17 is forcibly supplied from the gas supply tank 17 to the static fluid mixer 20 by starting the air supply pump 19 (gas supply process). The gas flows from the air supply pipe 23 through the air supply pump 19 into the mixing pipe 24, is mixed with the paint 10 in the mixing pipe 24, and then flows into the static fluid mixer 20 together with the paint 10. In the mixing pipe 24, the paint supplied by the water supply pump 18 and the gas supplied by the air supply pump 19 are mixed to produce the gas-mixed paint 10 (mixing process). The gas-mixed paint 10 flows into the static fluid mixer 20.

[0065] The controller receives the measured level measured by the level meter of the paint storage tank 16 and outputs (displays) a water injection message on the display when the measured level drops to the water injection level. The water injection message notifies the user of the need to inject paint 10 into the paint storage tank 16. The controller receives the measured flow rate measured by the flow meter and adjusts the output of the water supply pump 18 so that the measured flow rate becomes the target flow rate. The controller receives the measured air pressure measured by the barometer and adjusts the output of the air supply pump 19 so that the measured air pressure becomes the target air pressure.

[0066] The cooling device continuously cools the cylindrical unit 26 of the static fluid mixer 20 using a refrigerant while the nanobubble mixing device 15 is running (cooling process). The cooling device maintains the temperature of the cylindrical unit 26 at a set temperature (for example, 10 to 20°C). In the static fluid mixer 20, the gas-mixed paint 10 mixed with gas flows in from the inlet, and the gas-mixed paint 10 becomes a continuous phase fluid and a dispersed phase fluid by multiple honeycomb structure elements (agitating blades), and the continuous phase and dispersed phase fluids of the gas-mixed paint 10 flow while meandering through the honeycomb structure elements. The shear force received at that time breaks down the fluid (gas) as the dispersed phase, generating a finely divided mixed fluid.

[0067] Next, the flow of the generated finely divided mixed fluid is rectified, and the rectified finely divided mixed fluid flows while meandering through the honeycomb structure element arranged on the downstream side, and the finely divided mixed fluid (gas) as the dispersed phase is further refined by the shear force it receives at that time. Finally, the gas mixed into the paint 10 is ultra-refined to the nano level, nano-level bubbles (nanobubbles) are dispersed and mixed (dispersed and dissolved) into the paint 10, and nanobubbles 14 (a large number of independent fine spherical spaces) with a particle size of less than 1 μm are uniformly dispersed and mixed in at a predetermined concentration inside the paint 10 to produce a nanobubble-containing paint 10 (nanobubble-containing paint manufacturing process).

[0068] When the nanobubbles 14 are mixed into the paint, the temperature of the nanobubble-containing paint 10 in the cylindrical unit 26 in which the nanobubbles have been dispersed and mixed rises due to friction between the paint and the nanobubbles 14, but the temperature of the nanobubble-containing paint 10 in the cylindrical unit 26 is maintained at 10 to 20°C by cooling the cylindrical unit 26 with the cooling device. The paint 10 in which the nanobubbles 14 have been dispersed and mixed (dispersed and dissolved) is contained in the paint tank 21 through the supply pipe 25. The controller receives the measurement level measured by the level meter of the paint tank 21 and outputs (displays) the measurement level on a display. The amount of the paint 10 in which the nanobubbles 10 have been dispersed and mixed can be known from the measurement level outputted on the display.

[0069] Regarding the method of dispersing and mixing the nanobubbles 10 into the paint 10 (nanobubble generation method), any of the methods involving the flow of the paint 10, such as the swirling liquid flow type, static mixer type, ejector type, Venturi type, and pressurized dissolution type, can be used, and any of the methods not involving the flow of the paint 10, such as the fine hole type, rotation type, ultrasonic type, steam condensation type, and electrolysis type, can also be used.

[0070] The paint 10 (fluororesin paint, silicone resin paint, acrylic resin paint, urethane resin paint) has nanobubbles 14 (numerous independent tiny spherical spaces) dispersed (dispersed and dissolved) therein, and the nanobubbles 14 can reduce the proportion of the paint 10 itself per unit volume of the paint 10 (paint 10 with nanobubbles 14 dispersed (dispersed and dissolved)). This reduces the amount of paint 10 itself applied when the paint 10 (paint 10 with nanobubbles 14 dispersed (dispersed and dissolved)) is applied to the surface 12 of the substrate 11 to be coated, thereby reducing the amount of paint 10 applied to the substrate 11. In addition, the reduced amount applied reduces the unit price of the paint 10 per unit area of ​​the surface 12 of the substrate 11 compared to when the nanobubbles 14 are not dispersed in the paint 10, and the paint 10 can be applied (used) inexpensively.

[0071] The paint 10 has a reduced mass per unit volume compared to when the nanobubbles 14 (spherical spaces) are not dispersed and mixed (dispersed and dissolved) in it, and therefore when the paint 10 is applied to the surface 12 of the substrate 11 to be coated, the increase in weight of the substrate 11 including the coating film 13 formed from the paint 10 can be minimized.

[0072] The nanobubbles 14 dispersed (dissolved) in the paint 10 have an average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 is in the range of 1 nm or more and less than 300 nm. The maximum particle size distribution of the nanobubbles 14 inside the paint 10 is in the range of 50 nm or more and less than 500 nm, preferably in the range of 10 nm or more and less than 300 nm. The content of the nanobubbles 14 in the paint 10 in which the nanobubbles 14 are dispersed and mixed is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 90 vol.%. The total number of nanobubbles 14 per ml of the paint 10 is 10 7 ~10 12 The particle size and particle size distribution of the nanobubbles 14 in the coating material 10, the porosity, and the total number of nanobubbles 14 were measured by nanoparticle tracking analysis (NTA). With nanoparticle tracking analysis, the particle size distribution, particle number concentration, and aggregation state of the nanobubbles 14 in the coating liquid 10 can be measured with high resolution.

[0073] In the nanoparticle tracking analysis, the paint 10 containing nanobubbles 14 dispersed therein is placed in a sample chamber, and the sample chamber is irradiated with laser light. In the nanoparticle tracking analysis, the 90° scattered light of each nanobubble 14 irradiated with laser light is detected by a highly sensitive CMOS camera. The Brownian motion of the detected particles is observed as the movement of bright spots on the camera image and tracked. The diffusion coefficient is obtained by tracking this movement, and the particle size of the nanobubbles 14 is determined by the Stokes-Einstein equation. The particle distribution (concentration) is calculated by calculating the number of nanobubbles 14 per ml from all particle counts within the field of view of the camera, which has a known volume, and the content of nanobubbles 14 in the paint 10 and the total number of nanobubbles 14 per ml of the paint 10 are calculated. In the nanoparticle tracking analysis, the zeta potential of the particles is determined by measuring the electrophoretic mobility when a constant voltage is applied to the cell.

[0074] The paint 10 into which the nanobubbles 14 have been dispersed and mixed by the nanobubble mixing device 15 is filled with hydrogen ions H + Concentration and hydroxide ion OH - The properties regarding acid-base properties, which are approximately equal in concentration, are approximately neutral or alkaline. The nanobubbles 14 dispersed and mixed inside the paint 10 are mixed into the paint 10 in the form of spheres having high internal bubble pressure, and are negatively charged.

[0075] The nanobubbles 14 in the paint 10 have a diameter of less than 1 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The shape (sphere) of the nanobubbles 14 was observed using an atom probe field ion microscope (APFIM). The atom probe field ion microscope is a field ion microscope (FIM) equipped with a time-of-flight mass analyzer, and individual nanobubbles 14 are observed using the field ion microscope and identified by time-of-flight mass analysis. The shape (sphere) of the nanobubbles 14 in the paint 10 is reproduced with a resolution of approximately nanoscale level by displaying it three-dimensionally on a graphic workstation.

[0076] The nanobubbles 14 mixed inside the paint 10 rise slowly inside the paint 10. The rising speed of the nanobubbles 14 depends on the liquid properties of the paint 10, but in water, the nanobubbles have a diameter of about 100 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The rising speed U of a spherical bubble with a diameter d is expressed by the Stokes equation: U=pgd 2 / 18μ, where p is the liquid density, g is the gravitational acceleration, and μ is the liquid viscosity.

[0077] The nanobubbles 14 mixed (dissolved) inside the paint 10 have a high internal bubble pressure (self-pressurizing effect). The internal bubble pressure is higher than the pressure around the bubbles by ΔP according to the Young-Laplace equation: ΔP = 4σ / d due to the influence of surface tension σ. The relationship between the diameter d of the bubbles in the paint 10 and the internal bubble pressure is that the smaller the bubble, the higher the internal bubble pressure (3.87 "atm" for 1 μm, 29.7 "atm" for 100 nm, surface tension σ of water: 72.8 mN / m (20°C), pressure around the bubble is 1 "atm"). Therefore, when the bubbles shrink, the partial pressure of the dissolved gas components, that is, the driving force for dissolution, increases, and by reducing the gas to nano size, the gas becomes more easily dissolved in the paint 10, and a large amount of nanobubbles 14 dissolves in the paint 10.

[0078] The nanobubbles 14 mixed (dissolved) inside the paint 10 have a large gas-liquid interface area. The gas-liquid interface area per unit volume, A / V, is expressed by the formula: A / V = 6d. A / V increases as the bubble diameter d decreases, and this contributes greatly to the amount of gas mixed in (dissolved) in the paint 10. The amount of gas mixed in (dissolved) of the nanobubbles 14 is extremely large. The mass transfer rate N (mol / s) of the bubbles into the paint 10 is expressed by the formula: N = K G A(pp*), where KG is the gas-phase reference overall mass transfer coefficient (mol / m 2 sPa”, A is the surface area of ​​the bubble [m 2 ], p is the partial pressure of the dissolved component in the bubble (Pa), and p* is the partial pressure of the gas phase in equilibrium with the dissolved component in the liquid phase (Pa).

[0079] When the gas in the bubbles dissolves (mixes) into the paint 10, the overall mass transfer resistance is 1 / K L or 1 / K G H is the liquid phase resistance 1 / k L and gas phase resistance 1 / k G As a sum of H and Ohm's law of electrical resistance: 1 / K L =1 / K G H=1 / k L +1 / k G H. Here, K L is the liquid phase reference overall mass transfer coefficient, H is Henry's constant (p = H C ), formula: 1 / K L =1 / K G H=1 / k L +1 / k G If the gas-side mass transfer resistance 1 / kGH can be substantially ignored at H, the liquid-phase reference overall mass transfer coefficient KL and the liquid-side mass transfer coefficient kL become substantially equal.

[0080] For a spherical bubble, the Reynolds number Re<1 and the rising speed are as follows: U=pgd 2 Liquid phase mass transfer coefficient k when expressed as / 18μ L is the formula: L =D L / d[l+(1+dU / D L ) 1 / 3 ] where D L is the diffusion coefficient of the gas in the liquid phase, d is the bubble diameter, and U is the rising speed of the bubble. For example, the formula: L =D L +dl+[(1+dU / D L ) 1 / 3 ] by the bubble diameter and the liquid-side mass transfer coefficient k of the MB-water system L When the bubble diameter d is 100 μm, k L is 1.817 10 -4 "m / s", k when bubble diameter d is 10 μm L is 5.37·10 -4 "m / s", k when bubble diameter d is 1 μm L is 5.20·10 -3 The diffusion coefficient of oxygen in the paint 10 is D Lis 2.60 10 -9 "m 2 / s" was used.

[0081] k for the bubble diameter d L Using the value of N = K and the bubble internal pressure (atm) for the bubble diameter d, the formula is: G The mass transfer rate N was calculated using A(pp*), and the results showed that when the bubble diameter d was 10 μm, the upward velocity U was 3.26·10 -3 "m / min", pressure difference ΔP is 2.91·10 4 , bubble number ratio is 1.0·10 6 , area ratio is 100, mass transfer rate ratio is 6.15·10 4 "mol / s" and 1.0·10 8 "mol / mm", and when the bubble diameter d is 100 nm, the rising speed U is 3.15·10 -7 "m / min", pressure difference ΔP is 2.91·10 6 , bubble number ratio is 1.0·10 12 , area ratio is 1.0 10 4 , mass transfer rate ratio is 5.95 10 10 "mol / s" and 1.0·10 18 "mol / mm".

[0082] If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 10 μm, the number of bubbles will be 10 6 If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 100 nm, the number of bubbles will increase by 10. 12 The surface area of ​​a bubble with a diameter of 1 mm is increased to 10 4 Therefore, if the mass transfer rate (dissolution rate) per unit time of a bubble with a diameter of 1 mm is 1, then the mass transfer rate (dissolution rate) of a bubble with a diameter of 10 μm is 6·10 4 The mass transfer rate (dissolution rate) per unit time for a bubble with a diameter of 1 mm is 1, and for a bubble with a diameter of 100 nm, the mass transfer rate (dissolution rate) is 6·10 10In this way, the calculations show that as the bubbles become nano-sized, the surface area and the partial pressure inside the bubbles increase, and the rate of rise decreases, causing a rapid increase in the mass transfer rate (dissolution rate) for the paint 10.

[0083] The surface potential of the nanobubbles 14 was measured using electrophoresis experimental equipment. The negatively charged nanobubbles 14 generated in the container move in a zigzag pattern by switching the electric field direction of the electrodes introduced into the electrophoresis cell (thickness 1 mm, height 23.0 mm, width 75.0 mm) every 1 second. The bubble diameter was calculated using the Stokes equation by measuring the upward speed, and the zeta potential of the bubbles was calculated using the Smoluchowski equation: ζ=μu / ε by measuring the horizontal speed. Here, ζ is the zeta potential "V", μ is the viscosity of the paint 10 "kg / ms", and u is the mobility of the bubbles "m 2 / sV”, ε is the dielectric constant of paint 10, s 2 C 2 / kgm 3 "

[0084] The nanobubbles 14 are negatively charged at -30 to -40 "mV" regardless of their bubble diameter. The cluster structure of the paint 10 is formed from the paint 10 molecules and ionized + ions and - ions, and + ions and - ions tend to fit within the structure, but - ions in particular tend to accumulate at the interface, resulting in a negative charge. The negative charge of the nanobubbles 14 causes the nanobubbles 14 in the paint 10 to repel each other, and the nanobubbles 14 do not bond (unite) with each other due to electrostatic repulsion.

[0085] Since the nanobubbles 14 mixed (dissolved) in the paint 10 are negatively charged, the nanobubbles 14 dispersed and mixed in the paint 10 repel each other and do not bond (coalesce) with each other, which prevents the nanobubbles 14 from bonding together and becoming large bubbles, and the nanobubbles 14, which are ultrafine air bubbles, can be maintained in a dispersed state in the paint 10. Since the nanobubbles 14 do not bond (coalesce) with each other in the paint 10 and the ultrafine air bubbles 14 are dispersed and mixed (dispersed and dissolved) in the paint 10, the nanobubbles 14 are less likely to volatilize from the paint 10 and the nanobubbles 14 can remain in the paint 10 for a long period of time.

[0086] In the paint 10, the nanobubbles 14 are not bonded in a columnar shape, but are dispersed (dissolved) in a large amount at a predetermined concentration in the form of spheres having high internal bubble pressure. 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 A large amount of nanobubbles 14 having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed in the paint 10 at a predetermined concentration (high concentration), the content of the nanobubbles 14 in the paint 10 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 90 vol.%, and the total number of nanobubbles 14 per ml of the paint 10 is 10 7 ~10 12 Since the nanobubbles 14 are in the range of nanobubbles per 1 ml, the proportion of the paint 10 itself per unit volume in the paint 10 (paint 10 having nanobubbles 14 mixed in (dissolved)) can be reduced by the use of ultrafine bubbles 14, and the amount of paint 10 itself applied when the paint 10 (paint 10 having nanobubbles 14 mixed in (dissolved)) is applied to the surface 12 of the substrate 11 to be coated can be reliably reduced.

[0087] The paint 10 after the nanobubbles 14 are dispersed and mixed therein has a kinetic viscosity of 50 to 200 mm. 2 / s. Furthermore, the rising speed of the nanobubbles 14 inside the paint 10 at 20°C after the nanobubbles 14 are dispersed and mixed in is in the range of 0·000015 to 0.00005 mm / min. The nanobubbles 14 have an extremely small volume, so their rising speed inside the paint 10 is extremely slow. If the rising speed of the nanobubbles 14 inside the paint 10 exceeds 0.00005 mm / min, it is difficult to retain the nanobubbles 14 in the paint 10 for a long period of time, and the nanobubbles 14 may volatilize from the paint 10 within the target residence time.

[0088] The forces acting on the nanobubbles 14 inside the paint 10 include buoyancy and drag. Buoyancy is proportional to the volume of the nanobubbles 14 (proportional to the cube of the radius of the nanobubbles 14). Drag is proportional to the cross-sectional area of ​​the nanobubbles 14 (proportional to the square of the radius of the nanobubbles 14) and proportional to the square of the rising speed of the nanobubbles 14. Specifically, if the radius of the nanobubbles 14 is r, the density of the paint 10 is ρ, the gravitational acceleration is g, the viscosity of the paint 10 is η, and the moving speed of the nanobubbles 14 is u, then the buoyancy acting on the nanobubbles 14 (ignoring the density of the nanobubbles) is expressed by Archimedes' principle as follows: F=4πr 3 It is expressed by ρg / 3.

[0089] In addition, the resistance force acting on the nanobubbles 14 is expressed by the formula (2): F = 6πηru according to Stokes' theorem. From the formulas (1) and (2), the moving speed u of the nanobubbles 14 inside the paint 10 is expressed by the formula (3): u = (2 / 9)r 2 It is expressed by ρg / η. The rising speed of the nanobubbles 14 in the paint 10 was calculated from formula (3). As is clear from formula (3), the larger the radius r (particle size) of the nanobubbles 14, the higher the moving speed u of the nanobubbles 14 in the paint 10.

[0090] When the radius r of the nanobubble 14 under 1 atmospheric pressure is a, the radius r and the water depth h are calculated by the following formula (4): r = a × {101325 / (ρgh + 101325)} 1 / 3As is clear from formulas (3) and (4), the nanobubbles 14 have larger particle sizes and rise faster as the water depth of the paint 10 becomes shallower.

[0091] As a hypothesis, nanobubbles 14 (ultrafine bubbles) with a diameter of less than 1.0 μm have their solubility reduced by the salting-out phenomenon, and remain stable for a long period of time inside the paint 10. If nanobubbles 14 continued to exist stably for a long period of time due to the salting-out phenomenon, there would be no paint 10 containing nanobubbles 14 with a pH close to 7, but there are cases in which stable nanobubbles 14 exist even in neutral liquids.

[0092] Generally, when nanobubbles 14 are mixed with larger microbubbles, the nanobubbles 14 rise to the surface due to the influence of the latter larger microbubbles, or are affected by cavitation destruction due to external pressure, shortening the lifespan of the nanobubbles 14. However, when nanobubbles 14 are generated in the nanobubble mixing device 15, large microbubbles with diameters of 1.0 μm or more are not generated, so the lifespan of the generated nanobubbles 14 can be made longer.

[0093] (Substrate 11 (various items) to be coated) The article 11 to which the paint 10 is applied is a building, a metal molded product, a plastic molded product, a glass molded product, a rubber molded product, a leather molded product, a wood molded product, a paper molded product, a woven fabric molded product, or a nonwoven fabric molded product. The shapes of the building and these molded products are arbitrary (free). The buildings to which the paint 10 is applied include all kinds of buildings, as well as building materials such as mortar, concrete, ALC, siding boards, extruded cement boards, gypsum boards, slate, wood, and PC boards. Materials for metal molded products include iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, alloys, and the like. Metal molded products made of these materials can have various three-dimensional shapes such as plates, rods, and the like. Materials for plastic molded products include known thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyamide (nylon), vinyl chloride resin, acrylic resin, silicone resin, fluororesin, polyimide resin, polysulfone resin, etc., and thermosetting resins such as epoxy resin, melamine resin, phenol resin, unsaturated polyester resin, etc. Plastic molded products made from these materials come in various shapes, including film, sheet, plate, and other three-dimensional shapes.

[0094] (How to apply paint 10) The paint 10 is applied or sprayed onto a surface 12 (front and back) of a substrate 11 (various articles) to be coated. As an example of a method for applying a fluororesin paint, the substrate 11 is first degreased. The degreased treatment involves heating the substrate 11 in a furnace and baking it in an oven at a temperature higher than the baking temperature to thermally decompose the oils, grease, and dirt. Alternatively, solvent cleaning is performed to clean dirt and oil from substrates made of materials or with shapes that are not suitable for baking in an oven.

[0095] Next, surface preparation (pretreatment) is performed. In surface preparation, the surface 12 (painted surface) of the substrate 11 is blasted with Morundum or grit abrasives and air to remove rust, dirt, etc., and roughened to about 3 to 6 microns (blasting). Alternatively, in cases where blasting is not possible or in accordance with the function to be used, surface preparation for etching or chemical coating is performed. After the surface preparation, a primer is applied to the surface 12 (painted surface) of the substrate 11 to improve adhesion between the substrate 11 and the fluororesin (primer application). Next, the primer is baked using an oven (baking).

[0096] After baking, the fluororesin paint is applied to the surface 12 (coated surface) of the substrate 11 using a coating device such as a brush, roller, dipping, spray, roll coater, die coater, applicator, or spin coater. After the fluororesin paint is applied, it is dried to form a coating film. The drying temperature for the fluororesin paint is from room temperature to about 300°C. When the fluororesin paint is dried by heating, it is baked in a baking furnace.

[0097] Silicone resin paint, acrylic resin paint, and urethane resin paint are applied by a coating method suitable for the shape of the substrate 11 (various articles). For example, they are applied by spraying, dipping, brushing, roll coating, gravure coating, flexography, inkjet, etc. The drying temperature of silicon resin paint is about room temperature to 50°C. The drying temperature of acrylic resin paint is about room temperature to 120°C. The drying temperature of urethane resin paint is about room temperature to 100°C. When applying silicon resin paint, acrylic resin paint, and urethane resin paint, they may be blasted with grit abrasive grains and air to remove rust, dirt, etc., and may be subjected to a base treatment to roughen the surface to about 3 to 6 microns, as in the case of fluororesin paint.

[0098] Fluorine resin paint, silicon resin paint, acrylic resin paint, and urethane resin paint may be applied in a single layer or multiple layers. There is no particular limitation on the amount of fluororesin paint, silicon resin paint, acrylic resin paint, and urethane resin paint applied, and the amount is determined according to the surface performance required for the substrate 11 (various articles) to be applied. The coating film formed by drying the fluororesin paint, silicon resin paint, acrylic resin paint, and urethane resin paint has a coating thickness in the range of 60 to 300 μm, preferably 90 to 270 μm. The coating thickness of the coating film was measured using an electromagnetic thickness gauge, an eddy current thickness gauge, and an outside micrometer.

[0099] The nanobubbles 14 mixed (dissolved) inside the paint 10 applied to a specified film thickness (60 to 300 μm, preferably 90 to 270 μm) have a particle size that gradually increases from the bottom to the top of the paint 10 within the above range. Therefore, the particle size of the nanobubbles 14 located at the bottom of the paint 10 is the smallest, the particle size of the nanobubbles 14 located at the top of the paint 10 is the largest, and the particle size of the nanobubbles 14 located in the middle part of the paint 10 is intermediate between those of the nanobubbles 14 located at the bottom and the top.

[0100] (Formation of coating film 13 by paint 10) In the drying process after emulsion-based (water-based) paint 10 is applied to surface 12 (coated surface) of substrate 11, as shown in Fig. 5, the solvent (water) gradually evaporates, and the polymer particles dissolved in the solvent (water) deform and fuse together. Thereafter, interdiffusion of polymer chains occurs, completing film formation, and forming coating film 13 that is applied to surface 12 of substrate 11. The coating film 13 formed from emulsion-based paint 10 has a thickness in the range of 20 to 110 µm, preferably 30 to 90 µm.

[0101] Nanobubbles 14 with a particle size of less than 1 μm remain trapped inside the coating film 13 formed by drying and hardening the emulsion-based paint 10 on the surface 12 of the substrate 11 (various articles), without evaporating into the outside air, and the nanobubbles 14 are dispersed and mixed (dispersed and dissolved) at a predetermined concentration. The nanobubbles 14 dispersed and mixed inside the coating film 13 made from the emulsion-based paint 10 are spheres with high internal bubble pressure, just like when they were dispersed and mixed in the paint 10, and the average particle size D of the nanobubbles 14 is 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 The maximum particle size distribution of the nanobubbles 14 inside the coating film 13 made from the emulsion-based paint 10 is in the range of 50 nm to 500 nm, and preferably in the range of 10 nm to 300 nm. The content of the nanobubbles 14 in the coating film 13 made from the emulsion-based paint 10 in which the nanobubbles 14 are dispersed and mixed is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 90 vol.%, and the maximum particle size distribution of the nanobubbles 14 inside the coating film 13 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 90 vol.%. 2 The total number of nano bubbles per 14 is 10 7 ~10 12 It is in the range of pieces.

[0102] In the drying process after the solvent-based paint 10 is applied to the surface 12 (coated surface) of the substrate 11, as shown in Fig. 6, the solvent gradually evaporates, and the polymer chains dissolved in the solvent gradually shrink, causing mutual diffusion of the polymer chains, completing the film formation, and forming a coating film 13 that coats the surface 12 of the substrate 11. The nanobubbles 14 dispersed and mixed (dissolved) inside the solvent-based paint 10 are dispersed and mixed (dissolved) inside the coating film 13 without volatilizing into the outside air, and are trapped in the coating film 13. The coating film 13 formed from the solvent-based paint 10 has a film thickness in the range of 20 to 110 µm, preferably 30 to 90 µm.

[0103] The inside of the coating film 13 formed by drying and curing the solvent-based paint 10 on the surface 12 of the substrate 11 (various articles) contains particles with an average particle size D 90is less than 1 μm, preferably the average particle size D 50 The nanobubbles 14, which are in the range of 1 nm or more and less than 300 nm, remain and are trapped without evaporating into the outside air, and the nanobubbles 14 are dispersed and mixed (dispersed and dissolved) at a predetermined concentration. The nanobubbles 14 dispersed and mixed inside the coating film 13 made from the solvent-based paint 10 are spheres with high internal bubble pressure, just like when they were dispersed and mixed in the paint 10, and the average particle diameter D of the nanobubbles 14 is 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 The maximum particle size distribution of the nanobubbles 14 inside the coating film 13 made from the solvent-based paint 10 is in the range of 50 nm to 500 nm, and preferably in the range of 10 nm to 300 nm. The content of the nanobubbles 14 in the coating film 13 made from the solvent-based paint 10 in which the nanobubbles 14 are dispersed and mixed is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 90 vol.%, and the maximum particle size distribution of the nanobubbles 14 inside the coating film 13 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 90 vol.%. 2 The total number of nanobubbles per 14 is 10 7 ~10 12 It is in the range of pieces.

[0104] The nanobubbles 14 mixed (dissolved) inside the coating film 13 formed to a predetermined thickness (20 to 110 μm, preferably 30 to 90 μm) have a particle size that gradually increases from the bottom to the top of the coating film 13 within the above range. Therefore, the nanobubbles 14 located at the bottom of the coating film 13 have the smallest particle size, the nanobubbles 14 located at the top of the coating film 13 have the largest particle size, and the nanobubbles 14 located in the middle of the coating film 13 have a particle size intermediate between those of the nanobubbles 14 located at the bottom and the top. Note that the unevenness 35 initially formed on the surface 12 of the substrate 11 before coating with the coating film 13 is coated with the coating film 13, so that the surface 12 of the substrate 11 becomes smooth.

[0105] Fig. 7 is a diagram showing the porosity, total number of nanobubbles 14, and particle size of the nanobubbles 14 in the coating film 13 of samples (A) to (H), and Fig. 8 is a diagram showing the porosity, total number of nanobubbles 14, and particle size of the nanobubbles 14 in the coating film 13 of samples (I) to (P). Fig. 9 is a diagram showing evaluations of the adhesion, scratch hardness, abrasion resistance, and mass increase of the coating film 13 of samples (A) to (H), and Fig. 10 is a diagram showing evaluations of the adhesion, scratch hardness, abrasion resistance, and mass increase of the coating film 13 of samples (I) to (P).

[0106] The coating 10 forming the coating film 13 of Samples (A) to (I) contains dispersed and mixed (dispersed and dissolved) spherical nanobubbles 14. The coating 10 forming the coating film 13 of Samples (A) to (I) was applied to one side of a test piece by the above-mentioned application method, and the coating 10 was dried and cured to form the coating film 13 of Samples (A) to (I) having a film thickness (in the range of 20 to 110 μm, preferably 30 to 90 μm). The coating films 13 were evaluated for adhesion, scratch hardness, abrasion resistance, and mass increase as shown below.

[0107] (Method of Evaluating Adhesion of Coating Film 13 of Samples (A) to (L)) The adhesion test involved making a grid-like (25 squares) cut (grid pattern) in the coating film 13 of sample (A) to sample (L) made on one side of the test piece using a cutter knife and cutter guide, or a dedicated cutting tool. Next, cellophane tape was firmly pressed onto the grid pattern and then pulled away, and the adhesion was evaluated on a 6-point scale from the best classification 0 to the worst classification 5, with classifications 0 and 1 being ◯, classifications 2 and 3 being △, and classifications 4 and 5 being ×.

[0108] (Method of Evaluating Scratch Hardness of Coating Film 13 of Samples (A) to (L)) Scratch hardness is a test to check the hardness of a coating. The scratch hardness (pencil method) test method uses 14 levels of pencils from 6B to 6H to scratch the coating surface of sample (A) to sample (L) made on one side of the test piece at a 45° angle, and evaluates the pencil scratch value as the density symbol of the hardest pencil that does not cause any scratches on the coating. When evaluating a three-dimensional object where testing equipment cannot be used, scratch it by hand. H, 2H, 3H, 4H, 5H, 6H are rated as ◯, 2B, B, HB, F are △, and 6B, 5B, 4B, 3B are ×.

[0109] (Method of Evaluating Abrasion Resistance of Coating Film 13 of Samples (A) to (L)) The abrasion test method for the coating film 13 of Sample (A) to Sample (L) made on one side of the test piece was conducted by the Taber abrasion wheel method. In the abrasion wheel method, an abrasion wheel with a constant load was placed on a disk to which the test piece was fixed, and the degree of abrasion that occurred when rotating at a constant speed was evaluated by the number of times it was rotated until the base or undercoat was exposed or by the amount of abrasion loss after certain conditions. Small abrasion loss was evaluated as ◯, medium abrasion loss as △, and large abrasion loss as ×.

[0110] (Method of evaluating the increase in mass of test pieces on which the coating film 13 of samples (A) to (L) is formed) The mass of the test piece of Sample (A) to Sample (L) before the coating film 13 was formed was measured, and the mass of the test piece of Sample (A) to Sample (L) after the coating film 13 was formed on one side of the test piece was measured, and the mass of the test piece before the coating film 13 was formed was compared with the mass of the test piece after the coating film 13 was formed. If there was almost no change in the mass of the test piece after the coating film 13 was formed compared to the mass of the test piece before the coating film 13 was formed (if there was no increase in mass), it was judged as (absent), and if the mass of the test piece after the coating film 13 was formed compared to the mass of the test piece before the coating film 13 was formed, it was judged as (present).

[0111] The fluororesin coating 10 of sample A shown in FIG. 7 was applied to a test piece by the above-mentioned application method, and the fluororesin coating 10 was dried and cured to produce a fluororesin coating film 13 of sample A. The content of nanobubbles 14 was 60 vol.%, and the nanobubbles were 1 mm2 The total number of nano bubbles per 14 is 10 8 ~10 11 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the fluororesin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The fluororesin paint 10 of sample A that makes up the fluororesin coating film 13 of sample A has a nanobubble 14 content of 60 vol. %, and the total number of nanobubbles 14 per ml is 10 8 ~10 11 The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the fluororesin coating 10 in a spherical (spherical) state. The thickness of the fluororesin coating film 13 of sample A is 20 to 110 μm, and preferably 30 to 90 μm.

[0112] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the fluororesin paint 10 of sample A are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the fluororesin paint 10, and do not change into microbubbles. Furthermore, spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped) within the fluororesin coating film 13 of sample A that is created by drying and curing the fluororesin paint 10 of sample A.

[0113] The fluororesin coating film 13 made by applying the fluororesin paint 10 of sample A, in which spherical (spherical) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the fluororesin coating film 13 of sample A is made relative to the mass of the test piece before the fluororesin coating film 13 of sample A is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). Since the fluororesin coating film 13 made from the fluororesin paint 10 of sample A has excellent adhesion, scratch hardness, and abrasion resistance, even if the substrate 11 to which the fluororesin coating film 13 of sample A is applied is damaged in various ways, the fluororesin coating film 13 can protect the substrate 11 from various damages, and it was found that deterioration of the substrate 11 due to such damage can be prevented. Furthermore, it was found that even if the fluororesin paint 10 of sample A is applied to the surface 12 of the substrate 11 and then dried and cured to form a fluororesin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the fluororesin coating film 13 of sample A can be minimized.

[0114] The fluororesin coating 10 of sample B was applied to a test piece by the above-mentioned application method, and the fluororesin coating 10 was dried and cured to produce a fluororesin coating film 13 of sample B. The nanobubble 14 content was 85 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the fluororesin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The fluororesin paint 10 of sample B that is used to make the fluororesin coating film 13 of sample B has a nanobubble 14 content of 85 vol. % and a total number of nanobubbles 14 per ml of the paint. 8 ~10 12The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the fluororesin coating 10 in a spherical (spherical) state. The thickness of the fluororesin coating film 13 of sample B is 20 to 110 μm, and preferably 30 to 90 μm.

[0115] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the fluororesin paint 10 of sample B are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the fluororesin paint 10, and do not change into microbubbles. Furthermore, the fluororesin coating film 13 of sample B, which is created by drying and curing the fluororesin paint 10 of sample B, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0116] The fluororesin coating film 13 made by applying the fluororesin paint 10 of sample B, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the fluororesin coating film 13 of sample B is made relative to the mass of the test piece before the fluororesin coating film 13 of sample B is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). The fluororesin coating film 13 made from the fluororesin paint 10 of sample B has excellent adhesion, scratch hardness, and abrasion resistance, so that even if the substrate 11 to which the fluororesin coating film 13 of sample A is applied is damaged in various ways, the fluororesin coating film 13 can protect the substrate 11 from various damages, and it was found that deterioration of the substrate 11 due to such damage can be prevented. Furthermore, it was found that even if the fluororesin paint 10 of sample B is applied to the surface 12 of the substrate 11 and then dried and cured to form a fluororesin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the fluororesin coating film 13 of sample B can be minimized.

[0117] The silicone resin coating 10 of sample C was applied to a test piece by the above-mentioned application method, and the silicone resin coating 10 was dried and hardened to produce a silicone resin coating film 13 of sample C. The content of nanobubbles 14 was 60 vol.%, and 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 11 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the silicone resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The silicone resin paint 10 of sample C that makes the silicone resin coating film 13 of sample C has a nanobubble 14 content of 60 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 11 The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the silicone resin coating 10 in a spherical (spherical) state. The silicone resin coating film 13 of sample C has a thickness of 20 to 110 μm, preferably 30 to 90 μm.

[0118] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the silicone resin paint 10 of sample C are negatively charged, so they do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in the fluororesin paint 10, and the nanobubbles 14 do not change into microbubbles. Also, inside the silicone resin coating film 13 of sample C, which is created by drying and curing the silicone resin paint 10 of sample C, the spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0119] The silicone resin coating film 13 made by applying the silicone resin paint 10 of sample C, in which spherical (spherical) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the silicone resin coating film 13 of sample C is made relative to the mass of the test piece before the silicone resin coating film 13 of sample C is made (no increase in mass), and the evaluation of the increase in mass is (none) (see FIG. 9). Since the silicone resin coating film 13 made from the silicone resin paint 10 of sample C has excellent adhesion, scratch hardness, and abrasion resistance, even if the substrate 11 to which the silicone resin coating film 13 of sample C is applied is damaged in various ways, the silicone resin coating film 13 can protect the substrate 11 from various damages, and it was found that the deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the silicone resin paint 10 of sample C is applied to the surface 12 of the substrate 11 and then dried and cured to form a silicone resin coating 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the silicone resin coating 13 of sample C can be minimized.

[0120] The silicone resin coating 10 of sample D was applied to a test piece by the above-mentioned application method, and the silicone resin coating 10 was dried and hardened to produce a silicone resin coating film 13 of sample D. The content of nanobubbles 14 was 85 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the silicone resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The silicone resin paint 10 of sample D that makes the silicone resin coating film 13 of sample D has a nanobubble 14 content of 85 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 12The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the fluororesin coating 10 in a spherical (spherical) state. The thickness of the fluororesin coating film 13 of sample B is 20 to 110 μm, and preferably 30 to 90 μm.

[0121] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the silicone resin paint 10 of sample D are negatively charged, so they do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in the fluororesin paint 10, and do not change into microbubbles. Also, inside the silicone resin coating film 13 of sample D, which is created by drying and curing the silicone resin paint 10 of sample D, the spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0122] The silicone resin coating film 13 made by applying the silicone resin paint 10 of sample D, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the silicone resin coating film 13 of sample D is made relative to the mass of the test piece before the silicone resin coating film 13 of sample D is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). Since the silicone resin coating film 13 made from the silicone resin paint 10 of sample D has excellent adhesion, scratch hardness, and abrasion resistance, even if the substrate 11 to which the silicone resin coating film 13 of sample D is applied is damaged in various ways, the silicone resin coating film 13 can protect the substrate 11 from various damages, and it was found that the deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the silicone resin paint 10 of sample D is applied to the surface 12 of the substrate 11 and then dried and cured to form a silicone resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the silicone resin coating film 13 of sample D can be minimized.

[0123] The acrylic resin coating 10 of sample E was applied to a test piece by the above-mentioned application method, and the acrylic resin coating 10 was dried and cured to produce an acrylic resin coating film 13 of sample E. The content of nanobubbles 14 was 60 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 11 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the acrylic resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The acrylic resin paint 10 of sample E that makes the acrylic resin coating film 13 of sample E has a nanobubble 14 content of 60 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 11The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the acrylic resin coating 10 in a spherical (spherical) state. The thickness of the acrylic resin coating film 13 of sample E is 20 to 110 μm, and preferably 30 to 90 μm.

[0124] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the acrylic resin paint 10 of Sample E are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the acrylic resin paint 10, and do not change into microbubbles. Furthermore, the acrylic resin coating film 13 of Sample E, which is produced by drying and curing the acrylic resin paint 10 of Sample E, has spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0125] The acrylic resin coating film 13 made by applying the acrylic resin paint 10 of sample E, in which spherical (spherical) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the acrylic resin coating film 13 of sample E is made relative to the mass of the test piece before the acrylic resin coating film 13 of sample E is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). Since the acrylic resin coating film 13 made from the acrylic resin paint 10 of sample E has excellent adhesion, scratch hardness, and abrasion resistance, even if the substrate 11 to which the acrylic resin coating film 13 of sample E is applied is damaged in various ways, the acrylic resin coating film 13 can protect the substrate 11 from various damages, and it was found that deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the acrylic resin paint 10 of sample E is applied to the surface 12 of the substrate 11 and then dried and cured to form an acrylic resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the acrylic resin coating film 13 of sample E can be minimized.

[0126] The acrylic resin coating 10 of sample F was applied to a test piece by the above-mentioned application method, and the acrylic resin coating 10 was dried and cured to produce an acrylic resin coating film 13 of sample F. The content of nanobubbles 14 was 85 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the acrylic resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The acrylic resin paint 10 of sample F that makes the acrylic resin coating film 13 of sample F has a nanobubble 14 content of 85 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 12The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the acrylic resin coating 10 in a spherical (spherical) state. The thickness of the acrylic resin coating film 13 of sample F is 20 to 110 μm, and preferably 30 to 90 μm.

[0127] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the acrylic resin paint 10 of sample F are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the acrylic resin paint 10, and do not change into microbubbles. Furthermore, the acrylic resin coating film 13 of sample F, which is produced by drying and curing the acrylic resin paint 10 of sample F, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0128] The acrylic resin coating film 13 made by applying the acrylic resin paint 10 of sample F, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the acrylic resin coating film 13 of sample F is made relative to the mass of the test piece before the acrylic resin coating film 13 of sample F is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). Since the acrylic resin coating film 13 made from the acrylic resin paint 10 of sample F has excellent adhesion, scratch hardness, and abrasion resistance, it was found that even if the substrate 11 to which the acrylic resin coating film 13 of sample F is applied is damaged in various ways, the acrylic resin coating film 13 can protect the substrate 11 from various damages, and deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the acrylic resin paint 10 of sample F is applied to the surface 12 of the substrate 11 and then dried and cured to form an acrylic resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the acrylic resin coating film 13 of sample F can be minimized.

[0129] The urethane resin coating 10 of sample G was applied to a test piece by the above-mentioned application method, and the urethane resin coating 10 was dried and hardened to produce a urethane resin coating film 13 of sample G. The content of nanobubbles 14 was 60 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 8 ~10 11 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the urethane resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The urethane resin paint 10 of sample G that is used to make the urethane resin coating film 13 of sample G has a nanobubble 14 content of 60 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 11The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the urethane resin coating 10 in a spherical (spherical) state. The thickness of the urethane resin coating film 13 of sample G is 20 to 110 μm, and preferably 30 to 90 μm.

[0130] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the urethane resin paint 10 of sample G are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the urethane resin paint 10, and do not change into microbubbles. Furthermore, the urethane resin coating film 13 of sample G, which is produced by drying and curing the urethane resin paint 10 of sample G, has spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0131] The urethane resin coating film 13 made by applying the urethane resin paint 10 of sample G, in which spherical (spherical) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the urethane resin coating film 13 of sample G is made relative to the mass of the test piece before the urethane resin coating film 13 of sample G is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). The urethane resin coating film 13 made from the urethane resin paint 10 of sample G has excellent adhesion, scratch hardness, and abrasion resistance, so that even if the substrate 11 to which the urethane resin coating film 13 of sample G is applied is damaged in various ways, the urethane resin coating film 13 can protect the substrate 11 from various damages, and it was found that the deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the urethane resin paint 10 of sample G is applied to the surface 12 of the substrate 11 and then dried and cured to form a urethane resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the urethane resin coating film 13 of sample G can be minimized.

[0132] The urethane resin coating 10 of sample H was applied to a test piece by the above-mentioned application method, and the urethane resin coating 10 was dried and hardened to produce a urethane resin coating film 13 of sample H, which had a nanobubble 14 content of 85 vol.% and a nanobubble density of 1 mm. 2 The total number of nano bubbles per 14 is 10 8 ~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the urethane resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The urethane resin paint 10 of sample H that is used to make the urethane resin coating film 13 of sample H has a nanobubble 14 content of 85 vol. % and a total number of nanobubbles 14 per 1 ml. 8 ~10 12The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the urethane resin coating 10 in a spherical (spherical) state. The thickness of the urethane resin coating film 13 of sample H is 20 to 110 μm, preferably 30 to 90 μm.

[0133] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the urethane resin paint 10 of Sample H are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the urethane resin paint 10, and do not change into microbubbles. Furthermore, the urethane resin coating film 13 of Sample H, which is produced by drying and curing the urethane resin paint 10 of Sample H, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0134] The urethane resin coating film 13 made by applying the urethane resin paint 10 of sample H, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, on one side of the test piece has high adhesion, scratch hardness, and abrasion resistance, and is evaluated as ◯ for adhesion, scratch hardness, and abrasion resistance. There is no change in the mass of the test piece after the urethane resin coating film 13 of sample H is made relative to the mass of the test piece before the urethane resin coating film 13 of sample H is made (no increase in mass), and the evaluation of the increase in mass is (no increase) (see FIG. 9). The urethane resin coating film 13 made from the urethane resin paint 10 of sample H has excellent adhesion, scratch hardness, and abrasion resistance, so that even if the substrate 11 to which the urethane resin coating film 13 of sample H is applied is damaged in various ways, the urethane resin coating film 13 can protect the substrate 11 from various damages, and it was found that deterioration of the substrate 11 due to such damages can be prevented. Furthermore, it was found that even if the urethane resin paint 10 of sample H is applied to the surface 12 of the substrate 11 and then dried and cured to form a urethane resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 does not increase, and the increase in weight of the substrate 11 including the urethane resin coating film 13 of sample H can be minimized.

[0135] The fluororesin coating 10 of sample I was applied to a test piece by the above-mentioned application method, and the fluororesin coating 10 was dried and cured to produce a fluororesin coating film 13 of sample I. The nanobubble 14 content was 25 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 4 ~10 6 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the fluororesin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The fluororesin paint 10 of sample I that is used to make the fluororesin coating film 13 of sample I has a nanobubble 14 content of 25 vol. % and a total number of nanobubbles 14 per ml of the paint. 4 ~10 6The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the fluororesin coating 10 in a spherical (spherical) state. The thickness of the fluororesin coating film 13 of sample I is 20 to 110 μm, and preferably 30 to 90 μm.

[0136] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the fluororesin paint 10 of Sample I are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the fluororesin paint 10, and do not change into microbubbles. Also, inside the fluororesin coating film 13 of Sample I, which is created by drying and curing the fluororesin paint 10 of Sample I, the spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0137] The fluororesin coating film 13 created by applying the fluororesin paint 10 of sample I, which contains dispersed spherical nanobubbles 14 with particle sizes of 50 nm to 700 nm, to one side of a test piece has high adhesion, scratch hardness, and abrasion resistance, and is rated as good for adhesion, scratch hardness, and abrasion resistance. However, there is a change in the mass of the test piece after the fluororesin coating film 13 of sample I is created compared to the mass of the test piece before the fluororesin coating film 13 is created (there is an increase in mass), and the increase in mass is rated as good (see Figure 10). The fluororesin coating film 13 made from the fluororesin paint 10 of Sample I has excellent adhesion, scratch hardness, and abrasion resistance, so even if the substrate 11 to which the fluororesin coating film 13 of Sample I is applied is subjected to various types of damage, the fluororesin coating film 13 can protect the substrate 11 from the various types of damage. However, it was found that when the fluororesin paint 10 of Sample I is applied to the surface 12 of the substrate 11 and then dried and cured to form the fluororesin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 increases, and the increase in weight of the substrate 11 including the fluororesin coating film 13 of Sample I cannot be minimized.

[0138] The fluororesin coating 10 of sample J was applied to a test piece by the above-mentioned application method, and the fluororesin coating 10 was dried and cured to produce a fluororesin coating film 13 of sample J, which had a nanobubble 14 content of 98 vol.% and a nanobubble density of 1 mm. 2 The total number of nano bubbles per 14 is 10 9 ~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the fluororesin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The fluororesin paint 10 of sample J that is used to make the fluororesin coating film 13 of sample J has a nanobubble 14 content of 98 vol.%, and the total number of nanobubbles 14 per 1 ml is 10 9 ~10 12 The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the fluororesin coating 10 in a spherical (spherical) state. The thickness of the fluororesin coating film 13 of sample J is 20 to 110 μm, preferably 30 to 90 μm.

[0139] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the fluororesin paint 10 of Sample J are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the fluororesin paint 10, and do not change into microbubbles. Furthermore, the fluororesin coating film 13 of Sample J, which is produced by drying and curing the fluororesin paint 10 of Sample J, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0140] It was found that the fluororesin coating film 13 made by applying the fluororesin paint 10 of sample J, in which spherical (spherical) nanobubbles 14 with particle sizes of 100 nm to 800 nm are dispersed and mixed, to one side of a test piece does not increase the mass of the substrate 11 even if the fluororesin paint 10 of sample J is applied to the surface 12 of the substrate 11 and dried and cured to form the fluororesin coating film 13 on the surface 12 of the substrate 11, and the increase in the weight of the substrate 11 including the fluororesin coating film 13 of sample J can be minimized. However, the fluororesin coating film 13 of sample J has low adhesion, scratch hardness, and abrasion resistance, and is evaluated as × for adhesion, scratch hardness, and abrasion resistance. It was found that when the substrate 11 to which the fluororesin coating film 13 of sample J is applied is damaged in various ways, the fluororesin coating film 13 cannot protect the substrate 11 from various damages and cannot prevent the deterioration of the substrate 11 due to such damages.

[0141] The silicone resin coating 10 of sample K was applied to a test piece by the above-mentioned application method, and the silicone resin coating 10 was dried and hardened to produce a silicone resin coating film 13 of sample K. The content of nanobubbles 14 was 25 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 4 ~10 6 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the silicone resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The silicone resin paint 10 of sample K that is used to make the silicone resin coating film 13 of sample K has a nanobubble 14 content of 25 vol. % and a total number of nanobubbles 14 per 1 ml. 4 ~10 6 The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the silicone resin coating 10 in a spherical (spherical) state. The thickness of the silicone resin coating film 13 of sample K is 20 to 110 μm, preferably 30 to 90 μm.

[0142] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the silicone resin paint 10 of sample K are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the silicone resin paint 10, and do not change into microbubbles. Also, inside the silicone resin coating film 13 of sample K, which is created by drying and curing the silicone resin paint 10 of sample K, the spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0143] The silicone resin coating 13 created by applying the silicone resin paint 10 of sample K, which contains dispersed spherical nanobubbles 14 with particle sizes of 50 nm to 700 nm, to one side of a test piece has high adhesion, scratch hardness, and abrasion resistance, and is rated as good for adhesion, scratch hardness, and abrasion resistance. However, there is a change in the mass of the test piece after the silicone resin coating 13 of sample K is created compared to the mass of the test piece before the silicone resin coating 13 is created (there is an increase in mass), and the increase in mass is rated as good (see Figure 10). Since the silicone resin coating film 13 made from the silicone resin paint 10 of sample K has excellent adhesion, scratch hardness, and abrasion resistance, even if the substrate 11 to which the silicone resin coating film 13 of sample K is applied is subjected to various types of damage, the silicone resin coating film 13 can protect the substrate 11 from various types of damage. However, when the silicone resin paint 10 of sample K is applied to the surface 12 of the substrate 11 and dried and cured to form the silicone resin coating film 13 on the surface 12 of the substrate 11, it was found that the mass of the substrate 11 increases and the increase in weight of the substrate 11 including the silicone resin coating film 13 of sample K cannot be minimized.

[0144] The silicone resin coating 10 of sample L was applied to a test piece by the above-mentioned application method, and the silicone resin coating 10 was dried and hardened to produce a silicone resin coating film 13 of sample L. The content of nanobubbles 14 was 98 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 9~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the silicone resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The silicone resin paint 10 of sample L that makes the silicone resin coating film 13 of sample L has a nanobubble 14 content of 98 vol.%, and the total number of nanobubbles 14 per 1 ml is 10 9 ~10 12 The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the silicone resin coating 10 in a spherical (spherical) state. The thickness of the silicone resin coating film 13 of sample L is 20 to 110 μm, preferably 30 to 90 μm.

[0145] The spherical (spherical) nanobubbles 14 having a particle size of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the silicone resin paint 10 of sample L are negatively charged, so that the individual nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in the silicone resin paint 10, and do not change into microbubbles. Furthermore, the silicone resin coating film 13 of sample L, which is produced by drying and curing the silicone resin paint 10 of sample L, has spherical (spherical) nanobubbles 14 having a particle size of 100 nm to 800 nm dispersed and mixed (dispersed and dissolved) throughout (is trapped).

[0146] It was found that the silicone resin coating film 13 made by applying the silicone resin paint 10 of sample L, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, to one side of a test piece does not increase the mass of the substrate 11 even if the silicone resin paint 10 of sample L is applied to the surface 12 of the substrate 11 and dried and cured to create the silicone resin coating film 13 on the surface 12 of the substrate 11, and the increase in the weight of the substrate 11 including the silicone resin coating film 13 of sample L can be minimized. However, the silicone resin coating film 13 of sample L has low adhesion, scratch hardness, and abrasion resistance, and the adhesion, scratch hardness, and abrasion resistance are evaluated as ×. It was found that when the substrate 11 to which the silicone resin coating film 13 of sample L is applied is damaged in various ways, the silicone resin coating film 13 cannot protect the substrate 11 from various damages, and cannot prevent the deterioration of the substrate 11 due to such damages.

[0147] The acrylic resin coating 10 of sample M was applied to a test piece by the above-mentioned application method, and the acrylic resin coating 10 was dried and hardened to produce an acrylic resin coating film 13 of sample M. The content of nanobubbles 14 was 25 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 4 ~10 6 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the acrylic resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The acrylic resin paint 10 of sample M that makes the acrylic resin coating film 13 of sample M has a nanobubble 14 content of 25 vol. % and a total number of nanobubbles 14 per 1 ml. 4 ~10 6 The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the acrylic resin coating 10 in a spherical (spherical) state. The thickness of the acrylic resin coating film 13 of sample M is 20 to 110 μm, preferably 30 to 90 μm.

[0148] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the acrylic resin paint 10 of sample M are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the acrylic resin paint 10, and do not change into microbubbles. Furthermore, the acrylic resin coating film 13 of sample M, which is produced by drying and curing the acrylic resin paint 10 of sample M, has spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0149] The acrylic resin coating film 13 created by applying the acrylic resin paint 10 of sample M, which contains dispersed spherical nanobubbles 14 with particle sizes of 50 nm to 700 nm, to one side of a test piece has high adhesion, scratch hardness, and abrasion resistance, and is rated as good for adhesion, scratch hardness, and abrasion resistance. However, there is a change in the mass of the test piece after the acrylic resin coating film 13 of sample M is created compared to the mass of the test piece before the acrylic resin coating film 13 is created (there is an increase in mass), and the increase in mass is rated as good (see Figure 10). The acrylic resin coating film 13 made from the acrylic resin paint 10 of sample M has excellent adhesion, scratch hardness, and abrasion resistance, so even if the substrate 11 to which the acrylic resin coating film 13 of sample M is applied is subjected to various types of damage, the acrylic resin coating film 13 can protect the substrate 11 from such damage. However, it was found that when the acrylic resin paint 10 of sample M is applied to the surface 12 of the substrate 11 and then dried and cured to form the acrylic resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 increases, and it is not possible to minimize the increase in weight of the substrate 11 including the acrylic resin coating film 13 of sample M.

[0150] The acrylic resin coating 10 of sample N was applied to a test piece by the above-mentioned application method, and the acrylic resin coating 10 was dried and hardened to produce an acrylic resin coating film 13 of sample N having a nanobubble 14 content of 98 vol.% and a nanobubble density of 1 mm. 2 The total number of nano bubbles per 14 is 10 9~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the acrylic resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The acrylic resin paint 10 of sample N that makes the acrylic resin coating film 13 of sample N has a nanobubble 14 content of 98 vol.%, and the total number of nanobubbles 14 per 1 ml is 10 9 ~10 12 The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the acrylic resin coating 10 in a spherical (spherical) state. The thickness of the acrylic resin coating film 13 of sample N is 20 to 110 μm, preferably 30 to 90 μm.

[0151] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the acrylic resin paint 10 of Sample N are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the acrylic resin paint 10, and do not change into microbubbles. Furthermore, the acrylic resin coating film 13 of Sample N, which is produced by drying and curing the acrylic resin paint 10 of Sample N, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0152] It was found that the acrylic resin coating film 13 made by applying the acrylic resin paint 10 of sample N, in which spherical (spherical) nanobubbles 14 having a particle size of 100 nm to 800 nm are dispersed and mixed, to one side of a test piece does not increase the mass of the substrate 11 even if the acrylic resin paint 10 of sample N is applied to the surface 12 of the substrate 11 and dried and cured to create the acrylic resin coating film 13 on the surface 12 of the substrate 11, and the increase in the weight of the substrate 11 including the acrylic resin coating film 13 of sample N can be minimized. However, the acrylic resin coating film 13 of sample N has low adhesion, scratch hardness, and abrasion resistance, and the adhesion, scratch hardness, and abrasion resistance are evaluated as ×. It was found that when the substrate 11 to which the acrylic resin coating film 13 of sample N is applied is damaged in various ways, the acrylic resin coating film 13 cannot protect the substrate 11 from various damages, and cannot prevent the deterioration of the substrate 11 due to such damages.

[0153] The urethane resin coating 10 of sample O was applied to a test piece by the above-mentioned application method, and the urethane resin coating 10 was dried and hardened to produce a urethane resin coating film 13 of sample O. The content of nanobubbles 14 was 25 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 4 ~10 6 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the urethane resin coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm. The urethane resin paint 10 of sample O that is used to make the urethane resin coating film 13 of sample O has a nanobubble 14 content of 25 vol. % and a total number of nanobubbles 14 per 1 ml. 4 ~10 6 The nanobubbles 14 have a particle size of 50 nm to 700 nm per 1 ml and are dispersed and mixed (dispersed and dissolved) in the urethane resin coating 10 in a spherical (spherical) state. The thickness of the urethane resin coating film 13 of sample O is 20 to 110 μm, and preferably 30 to 90 μm.

[0154] The spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the urethane resin paint 10 of sample O are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the urethane resin paint 10, and do not change into microbubbles. Furthermore, the urethane resin coating film 13 of sample O, which is produced by drying and curing the urethane resin paint 10 of sample O, has spherical (spherical) nanobubbles 14 with diameters of 50 nm to 700 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0155] The urethane resin coating 13 created by applying the urethane resin paint 10 of sample O, which contains spherical (spherical) nanobubbles 14 with particle sizes of 50 nm to 700 nm dispersed therein, to one side of a test piece has high adhesion, scratch hardness, and abrasion resistance, and is rated as good for adhesion, scratch hardness, and abrasion resistance. However, there is a change in the mass of the test piece after the urethane resin coating 13 of sample O is created compared to the mass of the test piece before the urethane resin coating 13 is created (there is an increase in mass), and the increase in mass is rated as good (see Figure 10). The urethane resin coating film 13 made from the urethane resin paint 10 of sample O has excellent adhesion, scratch hardness, and abrasion resistance, so even if the substrate 11 to which the urethane resin coating film 13 of sample O is applied is subjected to various types of damage, the urethane resin coating film 13 can protect the substrate 11 from the various types of damage. However, it was found that when the urethane resin paint 10 of sample O is applied to the surface 12 of the substrate 11 and then dried and cured to form the urethane resin coating film 13 on the surface 12 of the substrate 11, the mass of the substrate 11 increases, and the increase in weight of the substrate 11 including the urethane resin coating film 13 of sample O cannot be minimized.

[0156] The urethane resin coating 10 of sample P was applied to a test piece by the above-mentioned application method, and the urethane resin coating 10 was dried and hardened to produce a urethane resin coating film 13 of sample P. The content of nanobubbles 14 was 98 vol.%, and the nanobubbles were 1 mm 2 The total number of nano bubbles per 14 is 10 9~10 12 pieces / 1mm 2 The nanobubbles 14 that are dispersed (dissolved) in the urethane resin coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm. The urethane resin paint 10 of sample P that makes up the urethane resin coating film 13 of sample P has a nanobubble 14 content of 98 vol. %, and the total number of nanobubbles 14 per 1 ml is 10 9 ~10 12 The nanobubbles 14 have a particle size of 100 nm to 800 nm per 1 ml and are dispersed and mixed (dissolved) in the urethane resin coating 10 in a spherical (spherical) state. The thickness of the urethane resin coating film 13 of sample P is 20 to 110 μm, and preferably 30 to 90 μm.

[0157] The spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout the urethane resin paint 10 of Sample P are negatively charged, so they do not bond (coalesce) with each other, do not become large bubbles in the urethane resin paint 10, and do not change into microbubbles. Furthermore, the urethane resin coating film 13 of Sample P, which is produced by drying and curing the urethane resin paint 10 of Sample P, has spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm that are uniformly dispersed and mixed (dispersed and dissolved) throughout (are trapped).

[0158] It was found that the urethane resin coating film 13 made by applying the urethane resin coating 10 of sample P, in which spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm are dispersed and mixed, to one side of a test piece does not increase the mass of the substrate 11 even if the urethane resin coating 10 of sample P is applied to the surface 12 of the substrate 11 and dried and cured to create the urethane resin coating film 13 on the surface 12 of the substrate 11, and the increase in the weight of the substrate 11 including the urethane resin coating film 13 of sample P can be minimized. However, the urethane resin coating film 13 of sample P has low adhesion, scratch hardness, and abrasion resistance, and is evaluated as x for adhesion, scratch hardness, and abrasion resistance. It was found that when the substrate 11 to which the urethane resin coating film 13 of sample P is applied is damaged in various ways, the urethane resin coating film 13 cannot protect the substrate 11 from various damages, and cannot prevent the deterioration of the substrate 11 due to such damages.

[0159] The paints 10 of Samples A to H (Fluororesin Paint 10, Silicone Resin Paint 10, Acrylic Resin Paint 10, and Urethane Resin Paint 10) have independent ultrafine particles (average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is 1 nm or more 500nm More preferably, the average particle size D 50 Since a large number of spherical nanobubbles 14 (spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed in (dispersed and dissolved) in the paint 10, the proportion of the paint 10 itself per unit volume of the paint 10 can be reduced by the large number of ultra-fine nanobubbles 14, and the amount of paint 10 itself applied when the paint is applied to the surface 12 of the substrate 11 (various articles) to be applied is reduced, making it possible to reduce the amount of paint 10 applied to the substrate 11. In addition, compared to a case in which the nanobubbles 14 (spherical spaces) are not dispersed and mixed in the paint 10, the reduced amount of paint 10 applied reduces the unit price of the paint 10 per unit area of ​​the surface 12 of the substrate 11, and the paint 10 can be applied inexpensively.

[0160] The paints 10 of Samples A to H (fluororesin paint 10, silicon resin paint 10, acrylic resin paint 10, urethane resin paint 10) have a reduced mass per unit volume compared to when nanobubbles 14 (spherical spaces) are not dispersed (dispersed and dissolved) in them, so when they are applied to the surface 12 of the substrate 11 to be coated, the increase in weight of the substrate 11 including the coating film 13 formed from the paint 10 can be minimized. Even if the substrate 11 (various articles) to which the coating film 13 formed from the paints 10 (fluororesin paint 10, silicon resin paint 10, acrylic resin paint 10, urethane resin paint 10) is applied is damaged in various ways, the coating film 13 can protect the substrate 11 from various damages, and deterioration of the substrate 11 due to the damage can be prevented.

[0161] The coating film 13 (fluororesin coating film 13, silicone resin coating film 13, acrylic resin coating film 13, urethane resin coating film 13) made from the paint 10 (fluororesin paint 10, silicone resin paint 10, acrylic resin paint 10, urethane resin paint 10) of samples A to H has independent ultrafine particles (average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 Since a large number of spherical nanobubbles 14 (spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are dispersed (dispersed and dissolved) in the coating film 13, the proportion of the coating film 13 itself per unit area of ​​the coating film 13 can be reduced by the large number of ultra-fine nanobubbles 14, and the amount of coating film 13 itself applied when the surface 12 of the substrate 11 (various articles) to be coated is reduced, making it possible to reduce the amount of coating film 13 applied to the substrate 11. In addition, compared to a case in which the nanobubbles 14 (spherical spaces) are not dispersed and mixed in the coating film 13, the reduced amount of coating reduces the unit price of the coating film 13 per unit area of ​​the surface 12 of the substrate 11, and the surface 12 of the substrate 11 can be coated with the coating film 13 at low cost.

[0162] The coating films 13 (fluororesin coating film 13, silicone resin coating film 13, acrylic resin coating film 10, urethane resin coating film 13) made from the paints 10 (fluororesin paint 10, silicone resin paint 10, acrylic resin paint 10, urethane resin paint 10) of Samples A to H have a reduced mass per unit area compared to when spherical nanobubbles 14 (spherical spaces) are not dispersed and mixed therein, and therefore, when the coating film 13 is applied to the surface 12 of the substrate 11 to be coated, the increase in weight of the substrate 11 (various articles) including the coating film 13 can be minimized. The coating films 13 (fluororesin coating film 13, silicone resin coating film 13, acrylic resin coating film 13, urethane resin coating film 13) made from the paints 10 (fluororesin paint 10, silicone resin paint 10, acrylic resin paint 10, urethane resin paint 10) of Samples A to H can protect the substrate 11 (various articles) to which they are applied from various types of damage, and can prevent deterioration of the substrate 11 due to such damage. [Explanation of symbols]

[0163] 10 paint 11 Goods 12 Surface 13 Coating 14 Nanobubbles 15 Nanobubble mixing device 16 Coating liquid storage tank 17 Gas supply tank 18 Water Pump 19 Air supply pump 20 Static fluid mixer (nanobubble generator) 21 Coating liquid storage tank 22 Water supply pipeline 23 Air supply line 24 Mixing line 25 Supply pipeline 26 Cylinder Unit

Claims

1. In a coating that is applied in a cured state to the surface of a substrate to be coated, The coating film is characterized in that a large number of minute, independent spherical spaces are dispersed and mixed inside the coating film.

2. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 The coating film according to claim 1, wherein the nanobubbles are dispersed and mixed in the coating film at a predetermined concentration.

3. The average particle size D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 The coating film according to claim 2, wherein the nanobubbles are dispersed and mixed in the coating film at a predetermined concentration.

4. The coating film according to claim 3, wherein the content of the nanobubbles in the coating film is in the range of 10 to 95 vol. %.

5. The coating film according to claim 4, wherein the coating film is any one of a fluororesin coating film made from a fluororesin paint, a silicone resin coating film made from a silicone resin paint, an acrylic resin coating film made from an acrylic resin paint, and a urethane resin coating film made from a urethane resin paint.

6. 6. The coating film according to claim 5, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these.

7. A coating material that is applied to a surface of a substrate to be coated and forms a coating film on the surface of the substrate, The paint is characterized in that a large number of minute, independent spherical spaces are dispersed and mixed inside the paint.

8. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 The coating material according to claim 7, wherein the nanobubbles are dispersed and mixed in the coating material at a predetermined concentration.

9. The nanobubbles are dispersed and mixed into the paint in a negatively charged state, and the average particle diameter D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 The coating material according to claim 8, wherein the nanobubbles are dispersed and mixed in the coating material at a predetermined concentration.

10. The coating material according to claim 8, wherein the content of the nanobubbles in the coating material is in the range of 10 to 95 vol. %.

11. The paint is any one of a fluororesin paint, a silicon resin paint, an acrylic resin paint, and a urethane resin paint, and the kinetic viscosity of the paint is 50 to 200 mm 2 11. The paint according to claim 10, wherein the nanobubbles have an ascending speed within the paint at 20° C. in the range of 0.000015 to 0.00005 mm / min.

12. The coating material according to claim 11, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these.

Citation Information

Patent Citations

  • Paint and base material with coating film

    JP2023052716A

Cited By

  • Paint manufacturing method and painting method

    JP7909326B1